An outer packaging material for a high-impact battery device

By controlling the crystal orientation distribution and alloy composition in the aluminum alloy foil, the crystal particle size of the aluminum-plastic composite film is optimized, which solves the deficiencies in the punching performance of the aluminum-plastic film and improves the formability and service life.

CN113927973BActive Publication Date: 2025-01-21JIANGXI RUIERGY NEW MATERIAL TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202111160533.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-09-30
Publication Date
2025-01-21
Estimated Expiration
2041-09-30

AI Technical Summary

Technical Problem

The existing aluminum-plastic composite films have shortcomings in the depth performance, especially when the Si content is too high, the crystalline nucleus becomes larger, resulting in rough surface of the aluminum foil, concentrated internal stress, and easy to rupture.

Method used

By controlling the crystal orientation distribution in the aluminum alloy foil and using EBSD to observe collective crystals with crystal orientation anisotropy, we ensure that the total ratio of Cube orientation, Cu orientation, s orientation, Bs orientation, and R orientation is more than 70%, and optimize the alloy composition. and crystal particle size, reducing the crystal particle size to less than 10.0 μm.

Benefits of technology

It improves the tensile strength, yield strength and elongation at break of the aluminum alloy foil, enhances the formability of the aluminum-plastic film, reduces the risk of rupture, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113927973B_ABST
    Figure CN113927973B_ABST
Patent Text Reader

Abstract

An outer packaging material for a high-depth battery device, comprising at least an outer base resin layer, an intermediate metal layer, and an inner heat-welded resin layer; the intermediate metal layer comprises an aluminum alloy foil, the aluminum alloy foil comprises aluminum (Al), iron (Fe), silicon (Si), copper (Cu), zinc (Zn), and titanium (Ti), wherein in the aluminum alloy foil: when using EBSD (electron beam backscattering analysis) to observe aggregate crystals with crystal orientation anisotropy, in the detection of the orientation distribution of the aluminum alloy foil surface, relative to the detected anisotropic The total of the ratio and the ratio without anisotropy, the total ratio of Cube orientation, Cu orientation, s orientation, Bs orientation, and R orientation is more than 70%; the total ratio of Cube orientation and Cu orientation is more than 30%; the ratio of Cube orientation is more than 10%; the average grain size is less than 10.0μm, the alloy components silicon (Si) is less than 0.05wt%, copper (Cu) is more than 0.004wt%, zinc (Zn) is less than 0.01wt%, and titanium (Ti) is less than 0.02wt%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an aluminum-plastic packaging film, in particular to an aluminum-plastic composite film for lithium battery packaging. Background Art

[0002] Currently, lithium-ion batteries are mainly divided into three categories: square, cylindrical, and soft-pack. The outer shells of square and cylindrical batteries are mainly made of hard shells such as aluminum alloy and stainless steel. The aluminum alloy outer shell can be pure aluminum, while the outer shell of the soft-pack battery is made of aluminum-plastic composite film, which greatly improves the problem of inflexible appearance design of hard-mounted batteries.

[0003] Aluminum-plastic composite film is the key material for soft-pack batteries. It can maintain high resistance in liquid chemical environments such as strong acids or organic solvents. Aluminum-plastic film is widely used in 3C and power batteries because of its advantages of light weight, thin thickness, and high energy density.

[0004] The aluminum-plastic composite film is composed of an outer layer of nylon, an intermediate layer of aluminum foil, and an inner layer of heat-sealed layer. As a battery outer packaging material, the aluminum-plastic film is required to have a high depth of punching performance, which can facilitate the stamping and forming of the battery shell. At the same time, the aluminum-plastic film is required to be free of cracks and pinholes during molding, so as to prevent leakage and other problems and ensure the service life of the battery.

[0005] The aluminum foil material in the aluminum-plastic composite film is mostly 8021 or 8079 series alloy material. The deep drawing performance of the aluminum-plastic film is related to the physical properties of each layer of material, especially the physical properties of the aluminum foil. Aluminum foil materials with different alloy compositions have different uses.

[0006] At present, the aluminum foil alloy materials used in battery soft pack aluminum plastic film are mainly 8021 and 8079. In terms of deep drawing performance, 8021 is generally better than 8079. Different series of aluminum foil materials have different alloy compositions. Please refer to Table 1 for the alloy composition of 8021:

[0007]

[0008] [Table 1] A8021 alloy composition ratio

[0009] From Table 1, we can see that the existing 8021 alloy features 1.2wt% to 1.7wt% Fe, followed by less than 0.15wt% Si. Since the raw material of alumina is a mixture of various alloys, it is better to say that Si is necessarily mixed into the raw material rather than adding Si to improve the material properties. However, if the Si content is not managed and controlled during the production process, it will affect the quality stability of the aluminum foil, so the target content of Si is usually controlled at around 0.1wt%.

[0010] The three factors that affect the deep drawing performance of aluminum foil are tensile strength, 0.2% yield point, and elongation. Among them, mechanical properties such as tensile strength and elongation are closely related to the precipitation state of Fe in the alloy composition. The factor affecting the precipitation state of Fe is the content of Si in the aluminum foil. In the production process of aluminum foil, Si has the effect of promoting the precipitation of Fe, and then forms an intermediate compound with Fe and Al, which acts as a recrystallization nucleus during annealing. Although the starting particle size of the crystal nucleus is mostly around φ1μm, the final crystal particle size is very small.

[0011] The main problem of existing A8021 materials is that when the Si content is too high, the crystal nucleus will become larger, resulting in coarsening of the crystal grains and uneven crystal grain size. If the internal grain size is coarse and uneven during deep drawing, the aluminum foil surface will be rough, stress will be concentrated in some places inside, and the thinner places will be deformed intensively, eventually leading to rupture.

[0012] At the same time, other alloy components such as copper (Cu), zinc (Zn), and titanium (Ti) are also added to the aluminum foil. In addition, in the aluminum foil manufacturing process, by combining the intermediate heat treatment after rough rolling (intermediate annealing process) and the heat treatment after final rolling (final annealing process), the grain size and aggregate crystal distribution can be controlled to improve the three factors that affect the deep drawing performance of the aluminum foil, namely, tensile strength, 0.2% yield point, and elongation.

[0013] Although the tensile strength and yield strength can be increased by reducing the grain diameter, the elongation at break, which has a greater impact on the deep drawing performance of the aluminum foil, tends to decrease. Therefore, the above method cannot achieve sufficient formability.

[0014] In addition, it is known that the crystal orientation distribution is Cube{001} <100> Direction, Cu{112} <111> and S{123} <643> , Bs (Brass) orientation, R orientation, etc. The orientation of these crystals has a great influence on the elongation at break. When the external force generates tensile stress, sliding occurs between the crystal orientations. The sliding phenomenon between the crystal orientations is divided into sliding in the thickness direction of the aluminum foil and sliding in the tensile stress direction. The sliding phenomenon in the thickness direction generally occurs in the direction of thinning due to stress. The sliding phenomenon in the thickness direction and the sliding phenomenon in the tensile stress direction must be balanced. In other words, the distribution of the collective crystal orientation needs to be controlled.

[0015] In order to stabilize the formability of aluminum foil and aluminum-plastic film composited with the aluminum foil, it is necessary to control the collective crystal orientation, added alloy components, crystal grain size, etc. Through the above management, the tensile strength, 0.2% yield point and elongation of the aluminum foil can be stabilized. Summary of the invention

[0016] The purpose of the present invention is to overcome the shortcomings of the prior art and provide an outer packaging material for a high-impact battery device, which is achieved by the following technical means:

[0017] An outer packaging material for a high-impact battery device, comprising at least an outer base resin layer, an intermediate metal layer, and an inner heat-welding resin layer; the intermediate metal layer comprises an aluminum alloy foil, the aluminum alloy foil comprises aluminum (Al), iron (Fe), silicon (Si), copper (Cu), zinc (Zn), and titanium (Ti), wherein in the aluminum alloy foil:

[0018] 1) When observing aggregate crystals with crystal orientation anisotropy using EBSD (electron beam backscattering analysis), in the detection of the orientation distribution on the aluminum alloy foil surface, the total ratio of the Cube orientation, Cu orientation, s orientation, Bs orientation, and R orientation is 70% or more, preferably 75% or more, relative to the total ratio of the detected anisotropy and non-anisotropy. ;

[0019] 2) When observing aggregate crystals with crystal orientation anisotropy using EBSD (electron beam backscattering analysis), in the detection of the orientation distribution on the aluminum alloy foil surface, the total ratio of the Cube orientation and the Cu orientation is 30% or more, preferably 45% or more, relative to the total ratio of the detected anisotropy and the ratio of the non-anisotropy;

[0020] 3) When observing aggregate crystals with crystal orientation anisotropy using EBSD (electron beam backscattering analysis), in the detection of the orientation distribution on the surface of the aluminum alloy foil, the ratio of the cube orientation is 10% or more, preferably 13% or more, relative to the total of the ratio with anisotropy and the ratio without anisotropy detected;

[0021] 4) The average size of the crystal grains is 10.0 μm or less, preferably 7.0 μm or less; and

[0022] 5) Based on the total weight of the aluminum alloy foil, the alloy components silicon (Si) is less than 0.05wt%, copper (Cu) is more than 0.004wt%, zinc (Zn) is less than 0.01wt%, and titanium (Ti) is less than 0.02wt%; further preferably, silicon (Si) is less than 0.02wt%, copper (Cu) is more than 0.010wt%, zinc (Zn) is less than 0.005wt%, and titanium (Ti) is less than 0.005wt%.

[0023] The outer packaging material for a high-impact battery device described above has a corrosion-resistant layer formed at least on the inner heat-welding resin layer side of the intermediate metal layer.

[0024] In the above-mentioned outer packaging material for a high-impact battery device, an outer adhesive layer is provided between the outer base resin layer and the intermediate metal layer.

[0025] In the above-mentioned outer packaging material for a high-impact battery device, an inner adhesive layer is provided between the intermediate metal layer and the inner heat-welding resin layer.

[0026] The above-mentioned outer casing material for a high-impact battery device, wherein the non-aqueous electrical device is formed by the above-mentioned outer casing material for a battery device.

[0027] In the above-mentioned outer packaging material for a high-strength battery device, the aluminum alloy foil further contains antimony (Sb) in an amount of 0.07 wt % or less.

[0028] The above-mentioned outer packaging material for high-depth battery devices, wherein, in the aluminum alloy foil, the direction parallel to the rolling direction is the flow direction, the direction orthogonal to the rolling direction is the width direction, and the direction at 45 degrees or 135 degrees to the flow direction and the width direction is the inclined direction; when a tensile test is performed with a tensile speed of 5.0 mm / min and an initial sample length of 50 mm, the 0.2% tensile strength (yield strength) in the flow direction, width direction, and inclined direction is 45 MPa or more, preferably 60 MPa or more, the elongation at break in the flow direction and width direction is 20% or more, preferably 30%, and the elongation at break in the inclined direction is 35% or more.

[0029] Compared with the prior art, the present invention has the following positive effects:

[0030] 1. By making the total ratio of the cube orientation, Cu orientation, s orientation, Bs orientation, and R orientation 70% or more, preferably 75% or more, relative to the total ratio of the detected anisotropic ratio and the non-anisotropic ratio, the sliding phenomenon in the thickness direction and the sliding in the tensile stress direction can be balanced, thereby improving the formability;

[0031] By making the total ratio of the Cube orientation and the Cu orientation 30% or more, preferably 45% or more, the fracture strength and the 0.2% yield strength can be stabilized and the formability can be maintained;

[0032] By making the ratio of the Cube orientation 10% or more, preferably 13% or more, the balance of the sliding phenomenon can be stabilized, the elongation at break can be improved, and the moldability can be improved;

[0033] By making the average size of the crystal grains less than 10.0 μm, preferably less than 7.0 μm, the crystal sliding space can be increased, the elongation at break can be improved, and the formability can be improved;

[0034] By making the alloy components silicon (Si) less than 0.05wt%, copper (Cu) more than 0.004wt%, zinc (Zn) less than 0.01wt%, and titanium (Ti) less than 0.02wt%. More preferably, silicon (Si) is less than 0.02wt%, copper (Cu) is more than 0.010wt%, zinc (Zn) is less than 0.005wt%, and titanium (Ti) is less than 0.005wt%, so that the crystal grain size can be refined, the grain size uniformity can be improved, and the formability can be better.

[0035] 2. Adding less than 0.07wt% of antimony (Sb) can reduce the grain size. When the grain size is smaller, the crystal sliding phenomenon occurs evenly, which can increase the fracture strength and yield strength, and improve the elongation at break.

[0036] 3. By controlling the 0.2% tensile strength (yield strength) in the flow direction, width direction, and inclined direction to be above 45 MPa, preferably above 60 MPa, the elongation at break in the flow direction and width direction to be above 20%, preferably 30%, and the elongation at break in the inclined direction to be above 35%, the relationship between strength and elongation can be balanced to achieve better formability. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 It is a schematic structural diagram of a preferred embodiment of the outer packaging material for a high-impact battery device of the present invention.

[0038] Figure 2 It is a schematic structural diagram of another preferred embodiment of the outer packaging material for a high-impact battery device of the present invention.

[0039] Component number description

[0040] 1 Outer base resin layer 6 Second corrosion resistant layer

[0041] 2 Outer adhesive layer 7 Inner adhesive layer

[0042] 3 Coloring layer 8 Internal heat-welding resin layer

[0043] 4 First corrosion resistant layer 81 Adhesive contact resin layer

[0044] 5 Intermediate metal layer 82 Innermost resin layer DETAILED DESCRIPTION

[0045] In the first embodiment of the present invention, please refer to Figure 1 , is a structural schematic diagram of a preferred embodiment of the outer packaging material for a high-impact battery device provided by the present invention, wherein the outer packaging material for a high-impact battery device comprises an outer base material resin layer 1; an intermediate metal layer 5, which is arranged under the outer base material resin layer 1; and an inner heat-melting resin layer 8, which is arranged under the intermediate metal layer 5.

[0046] The intermediate metal layer 5 is a barrier layer that can at least inhibit the infiltration of moisture; specifically, in the outer packaging material for lithium-ion batteries, the metal material used can be aluminum alloy, stainless steel, titanium steel, nickel-plated iron plate, etc.; when used as a metal foil, it can be one layer or multiple layers; preferably it contains at least one of aluminum alloy foil, nickel-plated iron plate and stainless steel foil.

[0047] The selection of aluminum alloy foil is as follows: from the viewpoint of improving the formability of lithium ion battery packaging materials, the aluminum alloy foil is preferably a soft aluminum alloy foil composed of annealed aluminum alloy, etc., and from the viewpoint of further improving the formability, the aluminum alloy foil is preferably an aluminum alloy foil containing iron. Silicon dioxide, magnesium, etc. may also be added according to the need for resistance to electrolytes, etc.

[0048] Examples of the stainless steel foil include austenitic, ferritic, austenitic ferritic, martensitic, and precipitation hardened stainless steel foils. From the viewpoint of providing a lithium ion battery packaging material having better formability, the stainless steel foil is preferably made of austenitic stainless steel.

[0049] Specific examples of the austenitic stainless steel constituting the stainless steel foil include SUS304, SUS301, and SUS316L. Among them, SUS304 is particularly preferred.

[0050] When the intermediate metal layer 5 is a metal foil, its thickness is at least sufficient to function to inhibit water intrusion, for example, the thickness is about 9-200 μm.

[0051] In some embodiments, the intermediate metal layer 5 is an aluminum alloy foil, and the alloy components other than aluminum (ALM) in the aluminum alloy foil mainly include iron (Fe), silicon (Si), copper (Cu), zinc (Zn), and titanium (Ti); preferably, the upper limit of the thickness of the intermediate metal layer 5 is preferably about 100 μm or less, and more preferably about 50 μm or less.

[0052] Aluminum alloy foil undergoes recrystallization under the influence of the rolling process (rough rolling process, final rolling process), heat treatment process (intermediate annealing process, final annealing process) and alloy composition described later in the manufacturing process, resulting in crystallization sites, sub-crystallization sites in non-alloy crystal state and unalloyed parts such as other added alloys. These crystallization sites and sub-crystallization sites can be observed using EBSD (electron beam backscattering analysis). In the crystallization sites, the anisotropy (aggregate structure) of the crystal orientation is significant. The anisotropy of the crystal orientation greatly affects the fracture strength, yield strength and elongation at break of the aluminum foil when subjected to tensile stress. Known crystallization orientations include Cube orientation, Cu orientation, S orientation, Bs orientation (Brass orientation), Gross orientation, R orientation, P orientation, etc.

[0053] In the analysis of crystal orientation, the grain boundary orientation difference of each orientation was determined to be 2° or more. In addition, 10 points in a range of 100 μm×100 μm were measured, and the maximum value was adopted.

[0054] In the detection of the surface orientation distribution of the aluminum alloy foil, there are two types of anisotropic sites and non-anisotropic sites. The non-anisotropic sites are mainly sub-crystallized sites and uncrystallized or non-alloyed sites with added alloy components. The sum of the ratio detected as having anisotropy and the ratio detected as non-anisotropic represents the sum of the crystallized sites, sub-crystallized sites, and non-crystallized or non-alloyed sites with added alloy components.

[0055] When tensile stress is generated by external force, sliding occurs between the crystal orientations. The sliding phenomenon between the crystal orientations is divided into sliding in the thickness direction of the aluminum foil and sliding in the tensile stress direction. Sliding in the thickness direction generally occurs in the direction where the thickness becomes thinner due to stress. The sliding phenomenon in the thickness direction and sliding phenomenon in the tensile stress direction must be balanced.

[0056] Therefore, the total ratio of the Cube orientation, Cu orientation, S orientation, Bs orientation and R orientation is less than 70% of the all-round distribution. At the same time, when the ratio of the Cu orientation to the Cube orientation exceeds 50%, the crystal orientation is in a state of dispersion. In particular, when the sliding phenomenon in the tensile stress direction increases, although the breaking strength and 0.2% tensile strength (yield strength) increase, the elongation at break decreases, so when used as a plastic film, the formability deteriorates.

[0057] When the ratio of Cube orientation to Cu orientation is less than 30%, S orientation, Bs orientation and R orientation become more. At this time, the tendency of the reduction of the breaking strength and 0.2% yield strength becomes greater. If the strength of the aluminum foil decreases, the formability becomes worse when used as an aluminum plastic film.

[0058] In the present embodiment, when EBSD (electron beam backscattering analysis) is used to observe collective crystals with crystal orientation anisotropy, the orientation distribution on the aluminum alloy foil surface is detected, and the total of the detected anisotropic ratio and non-anisotropic ratio includes the above-mentioned Cube orientation, Cu orientation, s orientation, Bs orientation, and R orientation.

[0059] 1) In some embodiments, the detection of the orientation distribution of the aluminum alloy foil shows that the total ratio of the Cube orientation, Cu orientation, s orientation, Bs orientation, and R orientation is greater than 70%, preferably greater than 75%.

[0060] 2) In some embodiments, the detection of the orientation distribution of the aluminum alloy foil shows that the total ratio of the Cube orientation and the Cu orientation is greater than 30%, preferably greater than 45%.

[0061] 3) In some embodiments, the detection of the orientation distribution of the aluminum alloy foil shows that the ratio of its Cube orientation is greater than 10%, preferably greater than 13%.

[0062] Cube orientation increases due to recrystallization during the rolling process (hot rolling process, cold rolling process) and heat treatment (intermediate annealing and final annealing) of the aluminum foil manufacturing process. When there are many cube orientations, stable sliding occurs between crystal orientations. Therefore, when it is less than 10%, the balance of sliding phenomenon deteriorates and the elongation at break tends to decrease. In the rolling process, when the thickness before rolling is 100%, the reduction rate (reduction rate) and temperature management after rolling, the temperature and time management such as the heating, insulation and cooling temperature of the intermediate annealing process and the final annealing process are important.

[0063] In this embodiment, the soft foil manufacturing process includes a casting process, a homogenization heat treatment process, a hot rolling process, a cold rolling process, an intermediate annealing process, a foil rolling process, a laminated foil rolling process, and a final annealing process, and is performed in this order. If necessary, the intermediate annealing process or the laminated foil rolling process can also be removed; the casting process is a process of melting and casting the aluminum alloy of the above composition using a conventional method to make an aluminum alloy ingot.

[0064] Homogenization heat treatment process

[0065] The homogenization heat treatment process is a process of homogenizing the aluminum alloy ingot. The homogenization heat treatment is carried out in order to subsequently hot-roll the ingot. In the present embodiment, the purpose is to precipitate fine Al-Fe intermetallic compounds, which has the effect of reducing the grain size. At the same time, it can also promote the development of the Cube orientation. When the soaking temperature of the homogenization heat treatment is lower than 400°C, the diffusion rate of the solid solution elements is extremely low, and the desired intermetallic compound distribution cannot be obtained, making the hot rolling process difficult. On the other hand, when the soaking temperature exceeds 550°C, the number of fine intermetallic compounds decreases.

[0066] Hot rolling process

[0067] The rolling completion temperature of the hot rolling process is 230-500°C. When the ingot after homogenization treatment is hot rolled, the completion temperature is very important. When it exceeds 500°C, part of the aluminum plate will recrystallize after hot rolling, and it will be difficult to obtain the ideal aggregate structure of the final product. The uneven structure of the mixed existence of subgrains and recrystallized grains will also lead to uneven grain structure in the final product, resulting in reduced formability. When the rolling completion temperature is less than 230°C, the temperature in the middle of hot rolling is very low, which may cause cracks at the end of the plate, and there is a risk of a significant reduction in productivity.

[0068] Cold rolling process

[0069] After the hot rolling process, cold working is performed, and at least one intermediate annealing can be performed during the cold working.

[0070] Intermediate annealing process

[0071] The intermediate annealing process generally refers to two methods: batch annealing (BATCH) in which the aluminum coil is placed in an annealing furnace and kept for a certain period of time, and rapid heating and rapid cooling annealing of the material through a continuous annealing line (CAL). Any of the above methods is acceptable, and CAL annealing is preferred. CAL annealing is more likely to refine the grains and directly affects the grain refinement after the final annealing. The preferred temperature for intermittent annealing is 300-400°C, and the preferred temperature for CAL annealing is 420-470°C. When the temperature of intermittent annealing is lower than 300°C, recrystallization cannot be completed. When it exceeds 400°C, the recrystallized grains are coarse and Fe precipitation may be insufficient. When the CAL annealing temperature is lower than 420°C, recrystallization cannot be completed. When it exceeds 470°C, the amount of dissolved Fe increases, which may cause the balance of all directions in the final product to be destroyed.

[0072] In CAL annealing, the intermediate annealing conditions can be set to, for example, a heating rate of 10 to 250°C / sec, a heating temperature of 400°C to 550°C, no holding time, or a holding time of 5 seconds or less, and a cooling rate of 20 to 200°C / sec.

[0073] When the heating rate is less than 10°C / second, the accumulated energy introduced during cold rolling during the heating process will be released, so the recrystallization nucleation rate decreases, the grain diameter after annealing becomes larger, and the elongation of the aluminum foil after final annealing decreases. When the heating rate is higher than 250°C / second, the effect is not significantly improved, but expensive heating equipment is required, which increases the production cost of the aluminum alloy plate. Therefore, the heating rate is preferably 10 to 250°C / second, and the more preferred lower limit is 20°C / second and the upper limit is 200°C / second. When the heating temperature is lower than 400°C, the time until the end of recrystallization becomes longer, which may lead to coarsening of the grains and a decrease in the manufacturing efficiency of the aluminum foil. If the heating temperature exceeds 550°C, the material may undergo local melting during annealing, resulting in a decrease in rollability and material properties. Therefore, the heating temperature is preferably 400°C to 550°C, and the more preferred lower limit is 420°C and the upper limit is 500°C.

[0074] In addition, although it is not necessary to set the holding time in particular, when the holding time exceeds 5 seconds, it is possible to cause the coarsening of recrystallized grains. Therefore, it is preferred that there is no holding time or the holding time is less than 5 seconds, and more preferably the holding time is less than 3 seconds. The continuous annealing line will quickly heat the material input from the inlet side, and will start cooling immediately after reaching the target temperature, so there is no so-called holding time sometimes.

[0075] Composite foil rolling process

[0076] The overlapping foil rolling process is a process of overlapping and rolling the hard foil after foil rolling. It means that in the final pass of foil rolling, two foils are overlapped and put into the rollers for rolling. There is no special regulation on the conditions of overlapping foil rolling, as long as the hard foil is rolled until the required foil thickness is reached. For example, overlapping foil rolling can be carried out under the condition of a reduction rate of 30 to 60%. The thickness of the foil after overlapping foil rolling can be 5 to 80 μm.

[0077] Final annealing process

[0078] The purpose of the final annealing process is to soften and improve the formability while balancing the density of each crystal orientation through recrystallization. In order to fully complete the recrystallization, the final annealing conditions are preferably 200-400°C and 1 hour or more. When it is lower than 200°C, the recrystallization may not be complete. When it exceeds 400°C, the recrystallized grains may be coarse or the adhesion between the foils may be too strong, and the foil roll cannot be unwound. 240-300°C and 2 hours or more are more preferred.

[0079] When the final reduction rate from intermediate annealing to the final product is 91-97%, an ideal aggregate structure and fine grain structure can be obtained. When the final reduction rate is less than 91%, the risk of recrystallized grain coarsening will increase, and when it exceeds 97%, the balance in all directions will be destroyed.

[0080] 4) In some embodiments, the average grain size of the aluminum alloy foil is less than 10.0 μm, preferably less than 7.0 μm.

[0081] When the average grain diameter exceeds 10.0μm, the external force generates tensile stress, and the amount of movement that the crystal can slide becomes smaller. The amount of movement affects the elongation. That is, the crystal cannot move under a small amount of stress, resulting in a smaller elongation at break; EBSD (electron beam backscattering analysis) was used in the measurement of the grain diameter and size distribution mentioned above.

[0082] 5) In some embodiments, the aluminum alloy foil has an alloy composition of silicon (Si) of less than 0.05wt%, copper (Cu) of more than 0.004wt%, zinc (Zn) of less than 0.01wt%, and titanium (Ti) of less than 0.02wt%. More preferably, silicon (Si) is less than 0.02wt%, copper (Cu) is more than 0.010wt%, zinc (Zn) is less than 0.005wt%, and titanium (Ti) is less than 0.005wt%.

[0083] It should be noted that the crystal orientation and grain size are greatly affected by the proportion of alloy components. When silicon (Si) exceeds 0.05wt%, the grain diameter will exceed 10μm, resulting in a decrease in the elongation at break. When copper (Cu) is lower than 0.004wt%, or zinc (Zn) is higher than 0.01wt%, the balance of grain diameter deteriorates, and the fracture strength and yield strength tend to decrease. When used as an aluminum-plastic film, the formability deteriorates; when titanium (Ti) exceeds 0.02wt%, although the fracture strength and yield strength increase, the elongation at break tends to decrease. When used as an aluminum-plastic film, the formability deteriorates.

[0084] 6) In some embodiments, the alloy composition further contains less than 0.07wt% antimony (Sb). By adding antimony (Sb), the crystal grain size can be reduced. When the grain diameter becomes smaller, the crystal sliding phenomenon occurs evenly, which can increase the fracture strength and yield strength, and improve the elongation at break. However, when the content exceeds 0.07wt%, precipitation occurs during recrystallization, which may have an impact on the human body, so it is not preferred.

[0085] 7) In some embodiments, in the aluminum alloy foil, the direction parallel to the rolling direction is the flow direction, the direction orthogonal to the rolling direction is the width direction, and the direction at 45 degrees or 135 degrees to the flow direction and the width direction is the inclined direction. When the tensile test is carried out at a tensile speed of 5.0 mm / min and an initial sample length of 50 mm, the 0.2% tensile strength (yield strength) in the flow direction, width direction, and inclined direction is 45 MPa or more, preferably 60 MPa or more, the elongation at break in the flow direction and width direction is 20% or more, preferably 30%, and the elongation at break in the inclined direction is 35% or more.

[0086] For aluminum foil for aluminum plastic film, tensile test needs to be carried out to measure the physical property that affects the formability of aluminum plastic film, i.e. breaking strength, 0.2% tensile stress (0.2% yield strength), elongation at break (elongation at break). Among the present invention, through various researches, above-mentioned breaking strength, elongation at break, 0.2% yield strength are applicable to find the aluminum foil that is most suitable for aluminum plastic film.

[0087] When the 0.2% yield strength in the flow direction, width direction, and oblique direction is less than 45 MPa, the strength is low and the steel sheet cannot withstand the molding stress during molding and is easily broken, resulting in poor moldability.

[0088] When the elongation at break in the flow direction and the width direction is less than 20% and the elongation at break in the oblique direction is less than 35%, the moldability is deteriorated due to the small elongation.

[0089] In the past, after adding alloy components, alloy components will be precipitated on the surface of aluminum alloy foil or in the annealing process performed after the rolling process, the volatility of rolling oil will be affected. Therefore, in the adjustment of alloy components, the management of surface cleanliness becomes very important. Surface cleanliness can be managed by a method using a wetting reagent to test wettability as an indicator or a method using a contact angle as an indicator. As an indicator of wettability, it is D grade and above, preferably B grade. In addition, as an indicator of contact angle, when tested with pure water, the contact angle is below 25°, preferably below 20°, and more preferably below 15°. When wettability is lower than D grade, or when the contact angle exceeds 25°, the reactivity or initial adhesion with the corrosion-resistant layer described later will be deteriorated. If the reactivity deteriorates, the reaction of the corrosion-resistant layer and the aluminum alloy foil layer becomes insufficient, and the resistance to the penetration of the electrolyte as the battery contents and the resistance to hydrogen fluoride produced in the reaction of the electrolyte and water will decrease. As time goes by, the adhesion of the corrosion-resistant layer to the aluminum alloy foil layer decreases, the corrosion-resistant layer dissolves, and the aluminum alloy foil layer and the corrosion-resistant layer are likely to peel off, thereby shortening the life of the battery.

[0090] On the other hand, the same situation will occur when the initial adhesion of the corrosion-resistant layer and the aluminum alloy foil layer deteriorates. The present invention can suppress the precipitation of alloy from the aluminum alloy foil by adjusting the alloy composition and making the alloy ratio within a certain range. In addition, in the annealing process during rolling, the management of temperature and time conditions can be made easy. In summary, by limiting the content combination of the four elements Fe, Si, Sb, and Cu in the aluminum alloy foil, the management of surface cleanliness becomes easy, and the durability, i.e., the electrolyte resistance, is stable, thereby extending the service life of the battery. The surface wettability test of the aluminum alloy foil layer can adopt "National Standard of the People's Republic of China GB / T225638.5-2016, Aluminum Foil Test Method, Part 5: Detection of Wettability". In addition, the contact angle test of the aluminum alloy foil layer can adopt "National Standard of the People's Republic of China GB / T22638.9-2008, Aluminum Foil Test Method Part 9: Hydrophilicity Measurement".

[0091] Please continue reading Figure 1 A second corrosion-resistant layer 6 is formed at least on the inner heat-melting resin layer 8 side of the intermediate metal layer 5; an outer adhesive layer 2 is provided between the outer base resin layer 1 and the intermediate metal layer 5; an inner adhesive layer 7 is provided between the intermediate metal layer 5 and the inner heat-melting resin layer 8; further, a coloring layer 3 is provided between the outer adhesive layer 2 and the intermediate metal layer 5, and a first corrosion-resistant layer 4 is provided between the coloring layer 3 and the intermediate metal layer 5, to form a non-aqueous electrical device with the aforementioned outer packaging material for the battery device.

[0092] Outer base resin layer 1 :

[0093] In this embodiment, the outer base resin layer 1 is provided for the purpose of being able to function as a base material of the lithium ion battery packaging material. The outer base resin layer 1 is located on the outer layer side of the lithium ion battery packaging material.

[0094] The material forming the outer base resin layer 1 is not particularly limited as long as it has at least insulating properties as a base material.

[0095] There are many methods for making the outer substrate resin layer 1, for example, it can be a resin film directly formed from resin, or it can be a coated resin product; as a resin film, it can be an unstretched film or a stretched film; as a stretched film, it can be a uniaxial stretched film or a biaxial stretched film, preferably a biaxial stretched film; as a method for making a biaxial stretched film, for example, a step-by-step biaxial stretching method, a blown film method, and a synchronous stretching method; as a resin coating method, for example, a roller coating method, a micro-concave coating method, an extrusion coating method, etc.

[0096] The resin forming the outer base resin layer 1 may be, for example, polyester, polyamide, polyolefin, epoxy resin, acrylic resin, fluororesin, polyurethane, silicone resin, phenolic resin or a modified product of the above resins; in addition, the resin forming the outer base resin layer 1 may be a copolymer of these resins, a modified product of the copolymer, or a mixture of these resins. The outer base resin layer 1 may be a single layer or multiple layers, preferably multiple layers.

[0097] As the resin forming the outer base resin layer 1, polyester and polyamide are preferably mentioned above.

[0098] As polyester, specifically, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polyethylene isophthalate, copolyester, etc. can be cited. In addition, as copolyester, copolyester with ethylene terephthalate as the main body of repeating unit can be cited. More specifically, copolymer polyester (hereinafter referred to as copolyester (terephthalate / isophthalate)) obtained by polymerizing ethylene terephthalate as the main body of repeating unit with ethylene isophthalate, copolyester (terephthalate / adipate), copolyester (terephthalate / sodium isophthalate), copolyester (terephthalate / phenyl-dicarboxylate), copolyester (terephthalate / decane dicarboxylate), etc. can be used alone or in combination of two or more.

[0099] Specific examples of polyamides include aliphatic polyamides such as nylon 6, nylon 66, nylon 610, nylon 12, nylon 46, and copolymers of nylon 6 and nylon 66; aromatic polyamides such as hexamethylenediamine-isophthalic acid-terephthalic acid copolymers such as nylon 6I, nylon 6T, nylon 6IT, and nylon 6I6T (I represents isophthalic acid, and t represents terephthalic acid) containing structural units derived from terephthalic acid and / or isophthalic acid, and polyamide MXD6 (polyamide PACM6 (polybis(4-aminocyclohexyl)methaneazideamide). The above polyamides may be used alone or in combination of two or more.

[0100] In some embodiments, the outer substrate resin layer 1 comprises a polyester film, a polyamide film or a polyolefin film; preferably, the outer substrate resin layer 1 comprises a stretched polyester film and a stretched polyamide film or a stretched polyolefin film; further preferably, the outer substrate resin layer 1 comprises a stretched polyethylene terephthalate film, a stretched polybutylene terephthalate film, a stretched nylon film or a stretched polypropylene film; more preferably, the outer substrate resin layer 1 comprises a biaxially stretched polyethylene terephthalate film, a biaxially stretched polybutylene terephthalate film, a biaxially stretched nylon film or a biaxially stretched polypropylene film.

[0101] The outer base resin layer 1 may be a single layer or may be composed of two or more layers. When the outer base resin layer 1 is composed of two or more layers, the outer base resin layer 1 may be a composite film formed by the action of an adhesive, or may be a resin composite film formed by co-extruding resins to form two or more layers. In addition, a resin composite film formed by co-extruding resins to form two or more layers may be used as the outer base resin layer 1 in an unstretched state, or may be used as the outer base resin layer 1 after uniaxial stretching or biaxial stretching.

[0102] In the outer substrate resin layer 1, as specific examples of a laminate of two or more resin films, there can be cited a composite film of a polyester film and a nylon film, a composite film of two or more nylon films, a composite film of two or more polyester films, etc. Preferably, the laminate comprises a laminate of a stretched nylon film and a stretched polyester film, a composite film of two or more stretched nylon films, or a composite film of two or more stretched polyester films. For example, when the outer substrate resin layer 1 is a two-layer resin composite film, a composite film of a polyester resin film and a polyester resin film, a composite film of a polyamide resin film and a polyamide resin film, or a composite film of a polyester resin film and a polyamide resin film is preferred, and a composite film of a polyethylene terephthalate film and a polyethylene terephthalate film, a composite film of a polybutylene terephthalate film and a polybutylene terephthalate film, a composite film of a nylon film and a nylon film, or a composite film of a polyethylene terephthalate film and a nylon film is more preferred. In addition, in a preferred embodiment, since polyester resin is difficult to change color when the electrolyte adheres to the surface, when the outer substrate resin layer 1 is a resin composite film with more than two layers, the polyester resin film is located at the outermost layer of the outer substrate resin layer 1.

[0103] When the outer substrate resin layer 1 is a resin composite film of more than two layers, the two or more resin films can also be composited by an adhesive. As a preferred adhesive, a glue having the same composition as the outer adhesive layer 2 can be used. In addition, as a method for composite two or more layers of resin films, there is no particular limitation, and dry composite method, sandwich composite method, extrusion composite method, thermal composite method, etc. can be used, preferably dry composite method. When composited by dry composite method, a reactive polyurethane adhesive is preferably used as the reactive adhesive of the outer layer. At this time, the thickness of the adhesive layer can be about 2-5μm. When the outer substrate resin layer is formed by a resin coating method, the resin can be first dissolved in an organic solvent, and the outer substrate resin layer 1 is formed by coating. The coating resin includes polyamide resin, polyimide resin, polyurethane resin, epoxy resin, acrylic resin, polyester resin, polyamide resin, polyimide resin, fluorine copolymer resin, polyester resin, etc. phenol resin, polyester resin, polycarbonate resin, urea resin or amino resin such as melamine resin.

[0104] Furthermore, one or more additives such as lubricants, flame retardants, anti-blocking agents, antioxidants, light stabilizers, tackifiers, antistatic agents, etc. may be added to the surface and inside of the outer base resin layer 1 .

[0105] From the viewpoint of improving the formability of the packaging material for lithium ion batteries, it is preferred to form a layer composed of a lubricant on the surface of the outer substrate resin layer 1. As a lubricant, there is no particular restriction, and an amide-based lubricant is preferred. Amide lubricants include saturated fatty acid amides, unsaturated fatty acid amides, substituted amides, hydroxymethylamides, saturated fatty acid bisamides, unsaturated fatty acid bisamides, fatty acid amides and aromatic bisamides, etc. Taking saturated fatty acid amides as an example, lauric acid amide, palmitic acid amide, stearic acid amide, behenic acid amide, hydroxystearic acid amide, etc. can be used. Taking unsaturated fatty acid amides as an example, oleic acid amide, erucic acid amide, etc. can be cited. Substituted amides include N-oleopalmitamide, N-stearamide, N-stearamide, N-oleostearamide and N-stearamide. In addition, hydroxymethylamides include hydroxymethylstearic acid amide, etc. Saturated fatty acid bisamides include methylene bis stearic acid amide, ethylene bis caprylic acid amide, ethylene bis lauric acid amide, ethylene bis stearic acid amide, ethylene bis hydroxy stearic acid amide, ethylene bis behenic acid amide and hexamethylene bis stearic acid hexamethylene bis behenic acid amide, hexamethylene hydroxy stearic acid amide, n, n'-distearyl adipic acid amide, n, n'-distearyl sebacic acid amide, etc. Unsaturated fatty acid bisamides include ethylene bis oleic acid amide, ethylene bis erucic acid amide, hexamethylene bis oleic acid amide, n, n'-dioleyl adipic acid amide and n, n'-dioleyl sebacic acid amide. Fatty acid ester amides include stearamide ethyl stearate, etc. In addition, aromatic bisamides include isophthalic acid amide, isophthalic acid amide, n, n'-distearyl isophthalic acid amide, etc. Lubricants can be used alone or in combination of two or more.

[0106] When a lubricant is present on the surface of the outer base resin layer 1, the amount of lubricant applied is not particularly limited, but is preferably about 3 mg / m 2 More preferably, 4-30 mg / m 2 about.

[0107] The lubricant present on the surface of the outer base resin layer 1 may be the lubricant seeping out of the outer base resin layer 1 containing the lubricant, or the lubricant may be applied on the surface of the outer base resin layer 1 .

[0108] The thickness of the outer base resin layer 1 is not particularly limited as long as it functions as a base. When the outer base resin layer 1 is a composite resin film of two or more layers, the thickness of each resin film constituting the layer is preferably about 2 to 30 μm.

[0109] In some embodiments, the outer substrate resin layer 1 can be a single layer or a composite film of more than two layers formed by one or more materials such as blown film nylon, synchronous or asynchronous biaxially stretched nylon, synchronous or asynchronous biaxially stretched polyethylene terephthalate (PET), synchronous or asynchronous biaxially stretched polybutylene terephthalate (PBT), polyimide (PI) and other polymer materials. The outer substrate resin layer 1 can be bonded to the intermediate metal layer 5 by one or a combination of extrusion, coating, compounding and thermal bonding. The total thickness of the outer substrate resin layer 1 is 5-35 μm; when the thickness is less than 5 μm, the formability and insulation are relatively poor. In addition, if it exceeds 35 μm, the total thickness of the metal composite film is too thick, and the advantage of the metal composite film, that is, the softness, will deteriorate.

[0110] Outer adhesive layer 2 :

[0111] See also Figure 1 In this embodiment, when the outer base resin layer 1 and the intermediate metal layer 5 are composited, an outer adhesive layer 2 is provided. The outer adhesive layer 2 is formed for the purpose of improving the adhesion between the outer base resin layer 1 and the intermediate metal layer 5, etc.

[0112] The outer adhesive layer 2 is formed by an adhesive capable of bonding the outer base resin layer 1 and the intermediate metal layer 5. The adhesive used to form the outer adhesive layer 2 is not limited, and can be, for example, a two-component curing adhesive (two-component adhesive), or a one-component curing adhesive (one-component adhesive). The adhesive used to form the outer adhesive layer 2 can be any of a chemical reaction type, a solvent volatilization type, a hot melt type, a hot pressing type, etc. In addition, the outer adhesive layer 2 can be a single layer or a multilayer.

[0113] The outer adhesive layer 2 is a two-component polyurethane adhesive formed by using polyester polyols and polyurethane-modified polyols as diol main agents and aromatic or aliphatic isocyanates as curing agents; the curing agent can be selected according to the functional groups of the bonding components, such as making an appropriate selection from multifunctional epoxy resins, polymers containing methanesulfonic acid, polyamine resins, inorganic acids, etc. In addition, the main agent used in the outer adhesive layer 2 includes polyester resins such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polyethylene isophthalate, and copolymerized polyester; polyether resin; polyurethane resin; epoxy resin; phenolic resin; polyamide resins such as nylon 6, nylon 66, nylon 12, and copolymerized polyamide; polyolefin resins such as polyolefin, cyclic polyolefin, acid-modified polyolefin, and acid-modified cyclic polyolefin; polyvinyl acetate; cellulose; (meth) acrylic resin; polyimide resin; polycarbonate; amino resins such as urea resin and melamine resin; rubbers such as chloroprene rubber, nitrile rubber, and styrene-butadiene rubber; silicone resin, etc. These adhesive components can be used alone or in combination of two or more.

[0114] More preferably, the combination of the outer adhesive layer 2 is one or two of a binary or polybasic polyester, a polyurethane-modified polyester and an isocyanate. Isocyanate is not limited to a compound having two or more isocyanate groups in a molecule. For example, a mixture of one or more polymers such as isophorone diisocyanate (IPDI), toluene diisocyanate (TDI), diphenylmethane-4,4'-diisocyanate (MDI), and 1,6-hexamethylene diisocyanate (HDI).

[0115] In addition, the outer adhesive layer 2 is allowed to add other ingredients as long as it does not hinder the adhesion, and may contain colorants, thermoplastic elastomers, tackifiers, fillers, etc. By containing a colorant in the outer adhesive layer 2, the packaging material for lithium-ion batteries can be colored. As a colorant, a colorant such as a pigment and a dye can be used. In addition, a single colorant can be used, or two or more can be mixed and used; the type of pigment is not particularly limited as long as it does not damage the adhesion of the outer adhesive layer 2. As an organic pigment, for example, azo, phthalocyanine, quinacridone, anthraquinone, dioxazine, indigothioindigo, perylene, isoindoline and other pigments can be used; as an inorganic pigment, carbon black, titanium oxide, cadmium, lead, isoindoline and other pigments can be used.

[0116] Among the colorants, carbon black is preferred in order to make the appearance of the lithium ion battery packaging material black. The average particle size of the pigment is not particularly limited, and can be about 0.05-5 μm, preferably about 0.08-2 μm. In addition, the average particle size of the pigment is the median particle size measured by a laser diffraction / scattering particle size distribution measuring device.

[0117] The pigment content in the outer adhesive layer 2 is not particularly limited as long as the lithium ion battery packaging material is colored, preferably about 5-60wt%, more preferably 10-40wt%; the thickness of the outer adhesive layer 2 is not particularly limited as long as it can bond the outer base resin layer 1 and the intermediate metal layer 5, as a preferred range, it can be listed as about 1-10μm, more preferably about 2-5μm.

[0118] Coloring layer 3 :

[0119] Please continue reading Figure 1 The colored layer 3 is a layer provided between the outer substrate resin layer 1 and the intermediate metal layer 5 as required. The colored metal composite film can be formed by directly adding a pigment to the outer adhesive layer 2, or the colored layer 3 can be formed between the outer substrate resin layer 1 and the outer adhesive layer 2. In addition, the colored layer 3 can also be provided on the outer side of the outer substrate resin layer 1.

[0120] The colored layer 3 can be formed, for example, by applying ink containing a colorant to the surface of the outer base resin layer 1, the surface of the outer adhesive layer 2, or the surface of the intermediate metal layer 5. As the colorant, a colorant such as a pigment or a dye can be used. In addition, the colorant can be used alone or in combination of two or more.

[0121] As specific examples of the colorant contained in the colored layer 3 , the examples described in connection with the outer adhesive layer 2 can be referred to.

[0122] The first corrosion resistant layer 4 and the second corrosion resistant layer 6 :

[0123] In this embodiment, a second corrosion-resistant layer 6 is further provided between the intermediate metal layer 5 and the inner heat-welding resin layer 8 to prevent the hydrogen fluoride generated by the reaction of the electrolyte and the water from corroding the surface of the intermediate metal layer 5, to prevent the intermediate metal layer 5 from separating from the inner heat-welding resin layer 8, and to maintain the uniformity of the surface of the intermediate metal layer 5, so that the adhesiveness (wettability) changes little, and has the effect of preventing the delamination between the intermediate metal layer 5 and the inner heat-welding resin layer 8 in the metal composite film. It is preferred to apply an anti-corrosion liquid to at least the surface of the intermediate metal layer 5 opposite to the outer substrate resin side to form the second corrosion-resistant layer 6, and it is preferred to form the first corrosion-resistant layer 4 and the second corrosion-resistant layer 6 on both sides of the intermediate metal layer 5. The first corrosion-resistant layer 4 is formed on the surface of the intermediate metal layer 5 in contact with the outer substrate resin layer 1, so that the surface uniformity of the intermediate metal layer 5 can be stabilized, the adhesiveness (wettability) changes can be reduced, and the metal composite film can be stored for a long time in a high temperature and high humidity environment, and the outer substrate resin layer 1 and the intermediate metal layer 5 have an anti-delamination effect.

[0124] As the first corrosion-resistant layer 4 or the second corrosion-resistant layer 6 formed by chemical conversion treatment, various anti-corrosion liquids are known, mainly containing phosphate, nitric acid, chromate, fluoride, rare earth oxide, and the like.

[0125] As chemical conversion treatment using phosphate and chromate, mainly include chromium chromate treatment, chromium phosphate treatment, phosphoric acid-chromate treatment, chromate treatment, etc., and as chromium compounds used for these treatments, chromium nitrate, chromium fluoride, chromium sulfate, chromium acetate, chromium oxalate, chromium diphosphate, chromium acetate, chromium chloride, chromium sulfate. Chromate treatment methods mainly include etching chromate treatment, electrolytic chromate treatment, coating type chromate treatment, etc., but coating type chromate treatment is preferred. In this coating type chromate treatment, on the degreased surface, a treatment liquid with a phosphate metal salt such as Cr (chromium) phosphate, Ti (titanium) phosphate, Zr (zirconium) phosphate, Zn (submetallic lead) phosphate and a mixture of these metal salts as the main component, or a treatment liquid with a phosphate nonmetal salt and a mixture of these nonmetal salts as the main component, is mixed with a synthetic resin as a treatment liquid, and is applied by a known coating method such as a roller coating method, a gravure printing method, and a dipping method, and dried. The treatment liquid can use various solvents such as water, alcohol solvents, hydrocarbon solvents, ketone solvents, ester compound solvents, ether solvents, etc., but water is preferred. In addition, as the resin component used therein, water-soluble polymers such as aminophenol or polyacrylic acid resin can be selected.

[0126] For example, the first corrosion-resistant layer 4 or the second corrosion-resistant layer 6 is formed by coating a particulate material in which metal oxides such as aluminum oxide, titanium oxide, cerium oxide, tin oxide and precipitated barium sulfate are dispersed in phosphoric acid on the surface of the intermediate metal layer 5 and sintering the material at above 150°C.

[0127] As other examples of the first corrosion-resistant layer 4 or the second corrosion-resistant layer 6, it mainly includes a film obtained by a coating-type corrosion-resistant treatment, and the coating-type corrosion-resistant treatment contains at least one component selected from the oxide sol of rare earth elements, anionic polymers, and cationic polymers. The coating agent may also contain phosphoric acid, phosphates, and a cross-linking agent for cross-linking polymers. In the rare earth element oxide sol, particles of rare earth element oxides (for example, particles with an average particle size of less than 100nm) are dispersed in a liquid dispersion medium. As rare earth element oxides, cerium oxide, yttrium oxide, neodymium oxide, lanthanum oxide, etc. are mainly contained. From the perspective of further improving adhesion, cerium oxide is preferred. The first corrosion-resistant layer 4 or the second corrosion-resistant layer 6 contains rare earth element oxides, which can be used alone or in combination of two or more. As a liquid dispersion medium for rare earth element oxide sols, various solvents such as water, alcohol solvents, hydrocarbon solvents, ketone solvents, ester compound solvents, and ether solvents can be used, preferably water. The cationic polymer mainly includes polyethyleneimine, a complex ion polymer formed by a polymer having polyethyleneimine and a carboxylic acid, a primary amine Graf-To acrylic resin grafted with a primary amine on an acrylic main chain, polyacetic acid or its derivatives, aminophenol, etc. In addition, the anionic polymer is preferably a co-polymer having poly(methyl)acrylic acid or its salt, or (methyl)acrylic acid and its salt as the main component. The crosslinking agent is preferably at least one of a compound having any functional chemical group of an isocyanate chemical group, a glycidyl chemical group, a carboxyl chemical group, an oxazoline chemical group, and a silane coupling agent.

[0128] In some embodiments, the first corrosion-resistant layer 4 or the second corrosion-resistant layer 6 is mainly composed of a trivalent chromium compound, an inorganic acid, a fluoride, an organic resin and water, wherein the ratio of the trivalent chromium compound, the inorganic acid, the fluoride and the organic resin is in the range of (19-60): (3-60): (0-10): (6-60). The ratio of the trivalent chromium compound to the organic resin is in the range of (3-100): 10;

[0129] The trivalent chromium compound in the corrosion-resistant liquid includes chromium nitrate, chromium phosphate, chromium fluoride or chromium chloride; the inorganic acid includes nitric acid and phosphoric acid; the fluoride includes chromium fluoride; the organic resin includes polyacrylic acid resin and polyvinyl alcohol; in some preferred embodiments, the polyacrylic acid resin includes polyacrylic acid, polymethyl acrylate, acrylic acid, maleic acid or a copolymer thereof, a copolymer of acrylic acid or styrene and its sodium salt, ammonium salt and other derivatives, wherein the weight average molecular weight of the polyacrylic acid resin is 10,000-800,000.

[0130] In some preferred embodiments, the first corrosion-resistant layer 4 or the second corrosion-resistant layer 6 is formed by coating a corrosion-resistant liquid mainly composed of a trivalent chromium compound, an inorganic acid, an organic resin, an organic solvent, and a titanate on the intermediate metal layer 5, wherein the ratio of the trivalent chromium compound, the inorganic acid, the organic resin, and the titanate is (25-38): (1-8): (10-12): (0-5). Among them, the ratio of the trivalent chromium compound to the organic resin is controlled within the range of (2-4): 1; the trivalent chromium compound includes chromium nitrate, chromium fluoride, chromium chloride, and chromium phosphate; the inorganic acid includes nitric acid and hydrofluoric acid; and the organic resin includes polyvinyl alcohol.

[0131] In some preferred embodiments, the first corrosion-resistant layer 4 or the second corrosion-resistant layer 6 is mainly composed of a resin containing an aminophenol polymer, a trivalent chromium compound and a phosphorus compound, wherein the ratio of the aminophenol polymer, the trivalent chromium compound and the phosphorus compound is 1:1 per m 2 The resin film layer contains about 1 to 200 mg of the aminated phenol polymer, about 0.5 to 50 mg of the trivalent chromium compound in terms of chromium, and about 0.5 to 50 mg of the phosphorus compound in terms of phosphorus. The aminated phenol polymer, the trivalent chromium compound, and the phosphorus compound may be the compounds listed above.

[0132] In this embodiment, the second corrosion-resistant layer 6 is formed on the side of the intermediate metal layer 5 contacting the inner adhesive layer 7, and the first layer is composed of cerium oxide, phosphoric acid or phosphate, and the first layer and the cationic or anionic polymer formed on the side of the inner adhesive layer 7 constitute at least two layers. In some preferred embodiments, the first layer is made of 1 to 100 parts by mass of phosphoric acid or phosphate relative to 100 parts by mass of acid value cerium. The phosphate, cationic or anionic polymer can use the substances shown above.

[0133] Examples of the fluoride include hydrofluoric acid, chromium fluoride, magnesium fluoride, elemental iron fluoride, cobalt fluoride, nickel fluoride, ammonium fluoride, titanium fluoride and its complex, zirconium fluoride salt or its complex, magnesium fluoride, ammonium hydrogen fluoride, etc. In this embodiment, chromium fluoride is preferred.

[0134] In this embodiment, the titanate includes titanous sulfate, titanium oxysulfate, ammonium titanium sulfate, titanium nitrate, ammonium titanium nitrate, titanium sulfate, fluorotitanic acid and its complex, ethyl acetoacetate, trimethylol alcohol, melamine, n-butylhydroquinone or a combination thereof, but is not particularly limited thereto.

[0135] Examples of the polyacrylic acid resin include polyacrylic acid, acrylic acid methacrylate copolymers, acrylic acid maleic acid copolymers, acetic acid styrene copolymers, or their sodium salts, ammonium salts, amine salts and other derivatives. Particularly preferred are derivatives of polyacrylic acid such as ammonium salts, sodium salts or amine salts of polyacrylic acid. Here, polyacrylic acid refers to a polymer of acrylic acid. In addition, the polyacrylic acid resin is preferably a copolymer of acrylic acid and a dicarboxylic acid or a dicarboxylic acid anhydride, and is also preferably an ammonium salt, sodium salt or amine salt of a copolymer of acrylic acid and a carboxylic acid or disulfuric anhydride. The polyacrylic acid resin may be used alone or in combination of two or more.

[0136] The weight average molecular weight of the polypropylene resin is preferably about 1,000 to 1,000,000, and more preferably about 3,000 to 800,000. The larger the molecular weight, the higher the corrosion resistance. However, the water solubility of the polyacrylic acid resin is low, the anticorrosive liquid prepared is unstable, and the production lacks stability. In addition, the smaller the molecular weight, the lower the corrosion resistance. In this embodiment, the weight average molecular weight of the polyacrylic acid resin is high in durability when it is above 1,000, and the manufacturing stability is good when it is below 1,000,000.

[0137] As the formation of the first corrosion-resistant layer 4 or the second corrosion-resistant layer 6, first, at least the inner heat-adhesive resin layer 7 of the intermediate metal layer 5 is degreased by using a treatment method such as an alkali immersion method, an electrolytic cleaning method, an acid cleaning method, an electrolytic acid cleaning method, an oxygen activation method, and a heat treatment (annealing treatment) during rolling. Secondly, in this embodiment, the corrosion-resistant liquid can be applied by a rod coating method, a roller coating method, a gravure coating method, a dipping method, etc., and a high-temperature chemical reaction is applied to the surface of the intermediate metal layer 5. The intermediate metal layer 5 coated with the corrosion-resistant liquid is heat-treated at a high temperature of 130-200°C for 0.5-5min to form the first corrosion-resistant layer 4 or the second corrosion-resistant layer 6.

[0138] The thickness of the first corrosion-resistant layer 4 or the second corrosion-resistant layer 6 is not particularly limited, but is preferably 1 nm-3.0 μm, and more preferably 1 nm-1.5 μm, from the perspective of the adhesion between the intermediate metal layer 5 and the outer substrate resin layer 1 or the inner heat-welding resin layer 8. In addition, the amount of chromium contained in the first corrosion-resistant layer 4 or the second corrosion-resistant layer 6 is between 8 mg / ㎡ and 50 mg / ㎡, and preferably between 10 mg / ㎡ and 30 mg / ㎡.

[0139] Inner adhesive layer 7 :

[0140] In the present embodiment, the inner adhesive layer 7 is an intermediate layer provided to firmly bond the intermediate metal layer 5 and the inner heat-welding resin layer 8 .

[0141] The inner adhesive layer 7 is formed of a resin capable of bonding the intermediate metal layer 5 and the heat-welding resin layer 8. The inner heat-welding resin layer 8 comprises polyolefin, cyclic polyolefin or modified polyolefin, and specifically, the modified polyolefin comprises carboxylic acid-modified polyolefin, carboxylic acid-modified cyclic polyolefin, methacrylic acid-modified polyolefin, acrylic acid-modified polyolefin, crotonic acid-modified polyolefin or imide-modified polyolefin.

[0142] From the viewpoint of improving the adhesion between the intermediate metal layer 5 and the inner heat-melting resin layer 8, as the modified polyolefin, acrylic acid, methacrylic acid, maleic acid, anhydrous maleic anhydride, polyamide and the like modified polyolefin resins are preferred. The resin constituting the inner adhesive layer 7 may or may not contain a polyolefin main chain, preferably containing a polyolefin main chain. Whether the resin constituting the inner adhesive layer 7 contains a polyolefin main chain can be analyzed by, for example, infrared spectroscopy, gas chromatography-mass spectrometry, etc., and the analysis method is not particularly limited. In some preferred embodiments, the polyolefin and its modified resin used in the inner adhesive are the same as the resin used in the inner heat-melting resin layer 8, which is a polypropylene resin or a copolymer of propylene and ethylene.

[0143] From the viewpoint of long-term use stability of the lithium ion battery packaging material, the inner adhesive layer 7 may be a resin composition containing an acid-modified polyolefin and a curing agent. The acid-modified polyolefin is particularly preferably a polyolefin modified with maleic anhydride or acrylic acid.

[0144] In the present embodiment, the curing agent is only required to cure the acid-modified polyolefin, and is not particularly limited, and includes epoxy curing agents, multifunctional isocyanate curing agents, carbodiimide curing agents, oxazoline curing agents and the like; in some embodiments, the epoxy curing agent is a compound having at least one epoxy group, but is not limited thereto, and includes bisphenol A diglycidyl ether, modified bisphenol A diglycidyl ether, novolac glycidyl ether, glycerol polyglycidyl ether or polyglycerol polyglycidyl ether; the multifunctional isocyanate curing agent is a compound having two or more isocyanate groups in the molecule, but is not limited thereto, and includes isophorone diisocyanate (PDI), hexamethylenetetramine (PET), polyisocyanate ... The polymerization and addition components of methyl diisocyanate (HDI), toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI) or their mixtures are reactants with other polymers; the carbodiimide curing agent is a compound having at least one carbodiimide group (-N=C=N-) in the molecule, but is not limited to this; the oxazoline curing agent is a compound having an oxazoline skeleton, but is not limited to this; in some preferred embodiments, the carbodiimide curing agent has at least two or more carbodiimide groups, and from the viewpoint of improving the adhesion between the inner adhesive layer 7 and the inner heat-melting resin layer 8, the curing agent can also be composed of two or more compounds.

[0145] The thickness of the inner adhesive layer 7 is not particularly limited as long as it can function as an adhesive layer, but is preferably about 1 to 80 μm, more preferably about 1 to 50 μm.

[0146] In this embodiment, the main component of the inner adhesive layer 7 is a single layer or two or more film layers formed by a mixture of one or more of modified polyolefin resin, polyolefin resin, block copolymer polypropylene resin (B-PP) with a polypropylene (PP) content exceeding 50wt%, random copolymer polypropylene resin (R-PP), and homopolymer polypropylene resin (H-PP).

[0147] When the intermediate metal layer 5 and the inner heat-welding resin layer 8 are compounded, the inner adhesive layer 7 may be formed by a solution-type inner adhesive layer or a hot-melt-type inner adhesive resin layer.

[0148] In some embodiments, a solution-type inner adhesive layer is used, wherein the solution-type inner adhesive layer is mainly composed of an acid-modified polyolefin resin and one or more of isocyanate, epoxy resin or oxazoline series as a hardener or an amine compound such as triethylamine, N,N-dimethylethanolamine as a hardener, and after being dissolved in at least one or more solvents such as water, ethanol, isopropanol, ethyl acetate, methyl ethyl ketone, toluene, methylcyclohexane, etc., it is evenly coated on the corrosion-resistant metal surface, heated to volatilize the solvent, and the thickness of the inner adhesive layer 7 reaches the desired effect, preferably about 1-10 μm, more preferably 1-5 μm. In the case of a thickness of less than 1 μm, the thickness becomes thinner, which will reduce the bonding force between the intermediate metal layer 5 and the inner heat-welding resin layer 8, making the bonding property a problem. When the thickness exceeds 10 μm, there is no problem with adhesion, but when the curing agent reacts, a hard resin layer will be formed, the bending resistance will be poor, the flexibility of the metal composite film will be reduced, and there is a risk of cracks when bending, and the intermediate metal layer 5 and the inner heat-welding resin layer 8 will peel off. The melting point of the acid-modified polyolefin resin in the solution-type inner layer adhesive is 60-155°C, the weight-average molecular weight is in the range of 10,000-150,000, and the acid value of the solution-type inner layer adhesive is in the range of 0.5-200 mg KOH / g. In the absence of a curing agent, the solution-type inner layer adhesive is mainly composed of an acid-modified polyolefin and an amine compound as a hardener, and the ratio of the acid-modified polyolefin to the amine compound is 10:1-125:1, preferably 15:1-50:1. The acid used for the modified polyolefin is maleic acid, fumaric acid, methacrylic acid, etc., and the amine compound is at least one of triethylamine or N, N-2 methylethanolamine. The acid-modified polyolefin is polypropylene with a melting point above 110° C. and a polypropylene content above 50 wt %.

[0149] If the melting point is below 60°C, the heat resistance is low, and the intermediate metal layer 5 and the inner heat-welding resin layer 8 may peel off at high temperatures. In addition, if it exceeds 155°C, the heat resistance is good, but when reacting with the curing agent, a hard resin layer will be formed, and the bending property is poor, so the flexibility of the metal composite film decreases, or cracks are generated when bending, and there is a case where the intermediate metal layer 5 and the inner heat-welding resin layer 8 peel off. If the weight-average molecular weight is below 10,000, the resin fluidity is high when heated, and the thickness will be seriously thinned during heat sealing, and the adhesion strength between the intermediate metal layer 5 and the inner heat-welding resin layer 8 (when the curing agent is added to react) will decrease, and there will be sealing problems. If the weight-average molecular weight exceeds 150,000, the intermediate metal layer 5 and the inner heat-welding resin layer 8 (when the curing agent is added to react) will form a hard resin layer, and the bending resistance will deteriorate, which will reduce the flexibility of the metal composite film, or cracks will be generated when bending, and there is a case where the intermediate metal layer 5 and the inner heat-welding resin layer 8 peel off. If the acid value of the acid-modified polyolefin resin is less than 0.5 mg KOH / g, the curing reaction points with the curing agent are small, and the adhesion between the intermediate metal layer 5 and the inner heat-welding resin layer 8 is unstable. If the acid value exceeds 200 mg KOH / g, the curing reaction between the curing agent and the acid-modified polyolefin resin is too intense, and a hard resin layer is formed, the bending resistance is deteriorated, the flexibility of the metal composite film is reduced, or cracks are generated when bent, and there is a possibility that the intermediate metal layer 5 and the inner heat-welding resin layer 8 are peeled off.

[0150] In other embodiments, a hot melt type inner adhesive layer is used, and the resin used in the hot melt type inner adhesive layer is an acid-modified polyolefin resin with a melting point of 135-165°C and an MFR (230°C) of 3-15g / 10min; the thickness of the formed inner adhesive layer 7 is 2-80μm, preferably 5-50μm. The degree of modification of the acid-modified polyolefin resin used in the hot melt type inner adhesive is 1%-15%, preferably 3%-12%. When the melting point of the acid-modified polyolefin resin is below 135°C, heating will cause the resin fluidity to increase, and when pressurized heat sealing, the thickness will be seriously thinned, and the adhesion strength between the intermediate metal layer 5 and the inner heat-melting resin layer 8 will become low, and there will be sealing problems. When the melting point is above 165°C, the fluidity is relatively low during pressurized heat sealing, and the heat resistance is improved. However, when compounded with the intermediate metal layer 5, the amount of heat shrinkage increases, which increases the internal stress and reduces the adhesion between the hot melt type inner layer adhesive and the intermediate metal layer 5. Therefore, if it is stored for a long time, it may peel off from the intermediate metal layer 5. In addition, due to the heating during heat sealing, heat shrinkage will occur further, the adhesion between the intermediate metal layer 5 will decrease, the sealing strength will decrease, and the sealing will become a big problem. If the MFR (230°C) of the acid-modified polyolefin resin is lower than 3g / 10min, it will be extruded and compounded on the intermediate metal layer 5, and the extrusion film forming property will be unstable. If the MFR (230°C) of the acid-modified polyolefin resin is higher than 15g / 10min, it will be extruded and compounded on the intermediate metal layer 5, heating will cause the resin fluidity to increase, and the thickness will be seriously thinned during pressurized heat sealing. The adhesion strength between the intermediate metal layer 5 and the inner heat-welded resin layer 8 will decrease, and there will be sealing problems.

[0151] Furthermore, when the thickness of the hot-melt type inner adhesive layer is less than 2 μm, the heat shrinkage cannot be absorbed when compounded with the intermediate metal layer 5 because the heat shrinkage is too much. Therefore, due to the increase in internal stress, the adhesion between the hot-melt type inner adhesive layer and the intermediate metal layer 5 is reduced. If it is stored for a long time, it may peel off from the intermediate metal layer 5. When the thickness of the hot-melt type inner adhesive layer exceeds 80 μm, there will be no physical property problems, but it will lead to an increase in production costs, so it is best to avoid using it. When the modification degree of the hot-melt type inner adhesive layer is less than 1%, the adhesion with the intermediate metal layer 5 will be unstable. If the modification degree exceeds 15%, although there will be no physical property problems, it will lead to an increase in production costs, so it is best to avoid this phenomenon.

[0152] Internal heat-welding resin layer 8 :

[0153] In the present embodiment, the inner heat-fusible resin layer 8 corresponds to the innermost layer, and is a layer (heat-sealing layer) that performs the function of heat-fusible resin layers 8 to seal the battery element when assembling the battery.

[0154] The resin constituting the inner heat-welding resin layer 8 is not particularly limited as long as it is heat-weldable, and is preferably a resin containing a polyolefin main chain such as polyolefin and acid-modified polyolefin.

[0155] As polyolefins, specifically, polyethylene ethylene-α-olefin copolymers such as low-density polyethylene, medium-density polyethylene, high-density polyethylene, and linear low-density polyethylene can be cited; polypropylene such as homopolypropylene, polypropylene block copolymers (such as block copolymers of propylene and ethylene), and random copolymers of polypropylene (such as random copolymers of propylene and ethylene); propylene-α-olefin copolymers; terpolymers of ethylene-butene-propylene, etc. Among them, polypropylene is preferred. The polyolefin resin used as a copolymer can be a block copolymer or a random copolymer. These polyolefin-based resins can be used alone or in combination of two or more.

[0156] Acid-modified polyolefin is a polymer modified by block polymerization or graft polymerization with an acid component and a polyolefin. As the acid-modified polyolefin, a copolymer formed by copolymerization of a polar molecule such as the above-mentioned polyacrylic acid or methacrylic acid with the above-mentioned polyolefin can also be used. In addition, as the acid component used in the acid modification, carboxylic acids or sulfonic acids such as maleic acid, acrylic acid, itaconic acid, crotonic acid, maleic anhydride, itaconic anhydride, and their anhydrides can be used, preferably acrylic acid or maleic acid and their anhydrides.

[0157] The inner heat-welding resin layer 8 may be composed of one resin alone or a combination of two or more resins. The inner heat-welding resin layer 8 may be composed of only one layer or two or more layers of the same or different resins.

[0158] The inner heat-welding resin layer 8 may also contain a lubricant or the like as required. When the inner heat-welding resin layer 8 contains a lubricant, the moldability of the outer packaging material for lithium-ion batteries can be improved. The type of lubricant is not particularly limited and can be selected and used within a known range. One type of lubricant may be used alone or two or more types may be used in combination.

[0159] The lubricant is not particularly limited, but an amide lubricant is preferably used. The lubricant may be used alone or in combination of two or more. The amide lubricant is preferably used on the surface of the outer base resin layer 1 .

[0160] When a lubricant is present on the surface of the inner heat-welding resin layer 8, the content thereof is not particularly limited, but from the viewpoint of improving the moldability of the electronic packaging material, 10 to 50 mg / m 2 , and more preferably 15-40 mg / m 2 .

[0161] The lubricant present on the surface of the inner heat-fusion resin layer 8 may be a lubricant seeping out from the resin constituting the inner heat-fusion resin layer 8 or a lubricant coated on the surface of the inner heat-fusion resin layer 8 .

[0162] The thickness of the inner heat-fusible resin layer 8 is not particularly limited as long as the heat-fusible resin layers 8 can perform the function of sealing the battery element after heat-fusion. It can be selected to be less than about 100 μm, and more preferably about 25-80 μm.

[0163] The inner heat-welding resin layer 8 may also contain ingredients such as antioxidants as needed. The inner heat-welding resin layer 8 containing an antioxidant can suppress thermal degradation during the manufacturing process. The type of antioxidant is not particularly limited and can be selected and used within a known range. The antioxidant can be used alone or in combination of two or more.

[0164] In this embodiment, the internal heat-melting resin includes acid-modified polyolefin resin, homopolymer polypropylene resin, block copolymer polypropylene resin, random copolymer polypropylene resin, polyethylene resin or a mixture of two or more thereof; the internal heat-melting resin layer 8 can be a single layer or a composite layer.

[0165] The resin used in the inner heat-welding resin layer 8 is a single layer or a composite layer composed of a mixture of one or more of the resins having a melting point of 120-162°C, more preferably 130-162°C; MFR (230°C) of 2-15g / 10min, more preferably MFR (230°C) of 3-12g / 10min, and a thickness of 20-120μm, more preferably 25-80μm. In addition, when the inner welding resin layer 8 is a composite layer, the thickness of the resin on the reverse side in contact with the intermediate metal layer 5 is more than 2μm, and the melting point is 130-152°C. When the melting point is below 120°C, the fluidity is high when heated, and when pressurized heat sealing is performed, the thickness becomes thinner, and the adhesion to the intermediate metal layer 5 decreases. In addition, the pressurization causes the squeezed resin inside the battery to flow to the unsqueezed edge part, and the expansion and contraction of the battery and the external force of the bending process cause cracks. The electrolyte will penetrate into the intermediate metal layer 5 through the cracks, causing the insulation resistance of the internal heat-welded resin layer 8 to decrease, leakage occurs, and the battery life will be shortened. When the melting point exceeds 162°C, the crystallinity of the resin increases, making the fluidity during pressurized heat sealing relatively low, and the heat resistance is improved, but when the high-crystalline resin is heat-sealed, a hard and brittle resin layer is formed. Therefore, under the conditions of expansion and contraction of the battery and the external force of the bending process, the resin layer is prone to cracking, and long-term stable sealing cannot be obtained. When the MFR (230°C) of the resin is lower than 2g / 10min, the fluidity of the resin is low during pressurized heat sealing, and it is difficult to obtain stable sealing. When the MFR (230°C) of the resin exceeds 15g / 10min, the resin fluidity is too high during pressurized heat sealing, the resin thickness becomes seriously thin, and it is difficult to obtain stable sealing. In addition, the pressurization causes the squeezed resin inside the battery to flow to the unsqueezed edge part, and the expansion and contraction of the battery and the external force of the bending process cause cracks. The electrolyte will penetrate into the intermediate metal layer 5 through the cracks, causing the insulation resistance of the inner heat-welding resin layer 8 to decrease, leakage occurs, and the battery life will be shortened. When the thickness of the inner heat-welding resin layer 8 is less than 20μm, it is difficult to obtain a uniform heat-welding part, and it is even more difficult to obtain a stable seal because the thickness cannot fully cover the deviation of the mechanical processing size and conditions of the heat sealing device. In addition, the pressurization causes the squeezed resin inside the battery to flow to the unsqueezed edge part, and the thickness of the inner heat-welding resin layer 8 becomes thinner. The expansion and contraction of the battery and the external force of the bending process easily cause cracks. The electrolyte will penetrate into the intermediate metal layer 5 through the cracks, causing the insulation resistance of the inner heat-welding resin layer 8 to decrease, leakage occurs, and the battery life will be shortened. When the thickness of the inner heat-welding resin layer 8 exceeds 120 μm, the water vapor permeability will increase, the moisture inside the battery will increase, and it will react with the electrolyte to produce gas, which is prone to expansion, rupture, and leakage. The battery life is reduced, and excessive hydrogen fluoride corrodes the corrosion-resistant metal layer, resulting in a decrease in the adhesion strength between the intermediate metal layer 5 and the inner heat-welding resin layer 8, which is prone to electrolyte leakage and other problems.

[0166] In a second embodiment of the present invention, the composite preparation method of the outer packaging material for a high-impact battery device includes: degreasing treatment, corrosion resistance treatment, outer layer adhesive treatment, and inner heat-welding layer composite treatment.

[0167] 1. Deoiling treatment: deoiling by annealing treatment above 150°C, plasma, corona method or alkali solution; wherein, the alkali deoiling method is to immerse the metal in alkali solution at 50-65°C, after a certain period of treatment, wash it twice with deionized water, and then dry it, so that the surface wettability of the deoiled metal intermediate metal layer 5 is 65mN / m, preferably above 70mN / m, or the contact angle of distilled water is below 15 degrees, preferably below 10 degrees. If the wettability or surface water contact angle of the intermediate metal layer 5 exceeds the given range, it means that the rolling oil in the manufacturing stage may still remain on the metal, resulting in the poor adhesion of the interface formed between the second corrosion-resistant layer 6, the intermediate metal layer 5 and the inner heat-welding resin layer 8. During the long-term storage of the battery, there is a risk of falling off between the intermediate metal layer 5 and the inner heat-welding resin layer 8, and battery leakage and the like are prone to occur.

[0168] 2. Corrosion resistance treatment: Anti-corrosion liquid is applied to the surface of the intermediate metal layer 5 and heat treated at high temperature for a period of time to form a first corrosion resistance layer 4 or a second corrosion resistance layer 6.

[0169] 3. Treatment of outer layer adhesive: a polyurethane adhesive dissolved in an organic solvent is coated on the contact surface between the intermediate metal layer 5 and the outer substrate resin layer 1, and heated at a certain temperature for a certain time to volatilize the organic solvent to form an outer layer adhesive layer 2, and further the outer substrate resin layer 1, the outer layer adhesive layer 2 and the intermediate metal layer 5 are compounded at a certain temperature and pressure, and after being stored at a certain temperature for a certain time, the outer layer adhesive layer 2 undergoes a curing reaction to obtain a composite resin layer consisting of the outer substrate resin layer 1, the outer layer adhesive layer 2 and the intermediate metal layer 5; when the outer substrate resin layer 1 and the intermediate metal layer 5 are compounded without using an outer layer adhesive, the intermediate metal layer 5 and the outer substrate resin layer 1 are compounded by heating and pressurizing, and the outer substrate resin layer 1 is filmized by heating treatment, ultraviolet treatment, and electron beam treatment, so as to obtain a composite resin layer consisting of the outer substrate resin layer 1 and the intermediate metal layer 5.

[0170] 4. Inner heat-melting layer composite treatment: The inner heat-melting resin layer 8 is composited with the composite film composed of the outer base resin layer 1 and the intermediate metal layer 5. The inner heat-melting layer composite method includes dry composite method, melt extrusion method, melt extrusion method or thermal bonding method.

[0171] Here, the inner heat-welding layer composite method is described by the following example:

[0172] a. Dry composite method: A solution-type inner layer adhesive composed of a main agent, a curing agent and an organic solvent is applied to the anti-corrosion surface of the intermediate metal layer 5 of the composite film composed of the outer substrate resin layer 1 and the intermediate metal layer 5, and the solution-type inner layer adhesive is dried to form an inner layer adhesive layer 7, and is thermally composited with the bonding surface of the inner heat-melting resin layer 8 at a certain temperature and pressure, and then subjected to a aging treatment to form a composite product of the outer substrate resin layer 1 / outer layer adhesive layer 2 / intermediate metal layer 5 / inner layer adhesive layer 7 / inner heat-melting resin layer 8. Preferably, the bonding surface of the inner heat-melting resin layer 8 in contact with the inner layer adhesive layer 7 is pre-corona treated. In addition, an aging treatment not exceeding 60°C of the melting point temperature of the inner layer adhesive layer 7 can be performed.

[0173] b. Melt extrusion method: The hot melt type inner layer adhesive resin is melt extruded to form a hot melt type inner layer adhesive layer of a certain thickness on the anti-corrosion surface of the intermediate metal layer 5. In addition, the surface of the inner layer adhesive layer 7 and the bonding surface of the inner heat-melting resin layer 8 are thermally compounded to form a composite product of outer base resin layer 1 / outer layer adhesive layer 2 / intermediate metal layer 5 / inner layer adhesive layer 7 / inner heat-melting resin layer 8. In order to improve the peeling force between the intermediate metal layer 5 and the inner heat-melting resin layer 8, a heat treatment of not more than 60°C of the melting point temperature of the inner layer adhesive layer 7 can be performed.

[0174] c. Melt extrusion method: The hot melt type inner adhesive layer and the inner heat-melting resin layer 8 are co-extruded to form a composite product of outer base resin layer 1 / outer adhesive layer 2 / intermediate metal layer 5 / inner adhesive layer 7 / inner heat-melting resin layer 8. After the surface of the intermediate metal layer 5 in contact with the inner adhesive layer 7 is subjected to corrosion resistance treatment, in order to improve the peeling force between the intermediate metal layer 5 and the inner heat-melting resin layer 8, a heat treatment not exceeding 60°C of the melting point of the inner adhesive layer 7 may be performed.

[0175] d. Thermal bonding method: Dissolve the resin main agent with a melting point above 100°C and the curing agent in an aqueous or organic solvent to form an aqueous solution type inner layer adhesive. Apply it to the corrosion-resistant surface of the metal layer of the composite layer composed of the outer substrate resin layer 1 and the intermediate metal layer 5, dry the solution type inner layer adhesive to form the inner layer adhesive layer 7. Under a certain temperature and pressure, thermally compound with the bonding surface of the inner heat-melting resin layer 8 to form a composite product of the outer substrate resin layer 1 / outer layer adhesive layer 2 / intermediate metal layer 5 / inner layer adhesive layer 7 / inner heat-melting resin layer 8. In order to improve the peeling force between the intermediate metal layer 5 and the inner heat-melting resin layer 8, a heat treatment of not more than 60°C of the melting point temperature of the inner layer adhesive layer 7 can be performed. The inner heat-melting resin layer 8 can also be formed by extrusion, or a film can be used. When a film is used, it is preferred that the bonding surface of the inner heat-melting resin layer 8 in contact with the inner layer adhesive layer 7 is pre-corona treated.

[0176] In a third embodiment of the present invention, the outer packaging material for a high-impact battery device is prepared by a composite method through a lamination method, and the method comprises the following steps:

[0177] Step S1: corona treatment is performed on the outer substrate resin layer 1 film in contact with the outer adhesive layer 2. Specifically, a non-crystalline polyester polyol with a weight average molecular weight of 5000, a Tg of 50°C, and a hydroxyl value of 25 mg KOH / g and a non-crystalline polyester polyol with a weight average molecular weight of 20000, a Tg of -17°C, and a hydroxyl value of 8 mg KOH / g are mixed in a weight ratio of 3:2, toluene diisocyanate (TDI) is added, and an outer layer adhesive solution with an NCO / OH ratio of 6.2 is formed and coated on the intermediate metal layer 5 to form an outer layer adhesive layer 2 (3 μm) on the intermediate metal layer 5.

[0178] Step S2: After the outer adhesive layer 2 and the outer substrate resin layer 1 film on the intermediate metal layer 5 are thermally laminated, they are aged at 80°C for 3 days to form the outer substrate resin layer 1 / outer adhesive layer 2 (3μm) / intermediate aluminum foil layer 5.

[0179] Step S3: Compounding the inner adhesive layer 7 and the inner heat-welding resin layer 8 on the aluminum foil surface of the outer base resin layer 1 / outer adhesive layer 2 (3 μm) / intermediate metal layer 5.

[0180] In some preferred embodiments of the third implementation aspect, the lamination method further comprises:

[0181] Step S1-1: Both sides of the intermediate metal layer 5 are pre-treated for corrosion resistance to form a first corrosion resistance layer 4 and a second corrosion resistance layer 6; specifically, the anti-corrosion liquid is evenly coated on both sides of the aluminum foil by a coating roller, and then heat-dried at 190°C for 2 minutes. The coating wet film amount of the corrosion resistance treatment liquid is 5g / m 2 The surface of the intermediate metal layer 5 is coated with chromium (Cr) with a content of 15 mg / m 2 The aluminum foil used has a thickness of 40 μm and a water contact angle of 15°. The annealed intermediate metal layer 5 has a surface content of chromium nitrate, phosphoric acid and acrylic resin in a ratio of 2:2:1.

[0182] In a preferred embodiment, the inner adhesive layer 7 can be formed by a melt-type inner adhesive layer compounding method: the melt-type resin used in the inner adhesive layer 7 is anhydrous maleic anhydride-modified polypropylene, and an inner adhesive layer 7 with a thickness of 15 μm is formed on the second corrosion-resistant layer 6, and further compounded with an inner heat-melting resin with a thickness of 30 μm. The inner adhesive layer 7 and the heat-melting resin layer 8 are compounded on the corrosion-resistant surface of the intermediate metal layer 5 in contact with the inner heat-melting resin layer 8, that is, the second corrosion-resistant layer 6, by melt co-extrusion. The inner adhesive layer 7 used is 60wt% (by weight) of anhydrous maleic anhydride modified random copolymer polypropylene with a melting point of 140°C and an MFR (230°C) of 5g / 10min. The modification degree of anhydrous maleic anhydride on the random copolymer polypropylene is 10%, the melting point is 160°C, the MFR (230°C) is 2.6g / 10min, and the density is 0.87g / cm 3 24 wt% (by weight) of a copolymer elastomer of propylene and butene, with a melting point of 130°C, an MFR (230°C) of 9.5 g / 10 min, and a density of 0.91 g / cm 3 A mixture of 8 wt% (by weight) of a crystalline copolymer elastomer of ethylene and propylene and 8 wt% (by weight) of a low-density polyethylene having a melting point of 105°C and an MFR (230°C) of 12 g / 10min.

[0183] After the intermediate metal layer 5 is compounded with the inner adhesive layer 7 and the inner heat-melting resin layer 8, a heat treatment is performed at a temperature of 180°C for 2 seconds. Thus, a composite product of outer base resin layer 1 / outer adhesive layer 2 (3 μm) / intermediate metal layer 5 / inner adhesive layer 7 (15 μm) / inner heat-melting resin layer 8 (30 μm) is formed.

[0184] In some other embodiments of this embodiment, the inner heat-melting resin layer 8 is further composed of two layers. Figure 2 The inner heat-melting resin layer 8 has a structure of: an adhesive contact resin layer 81 and an innermost resin layer 82, wherein the adhesive contact resin layer 81 is a resin layer in contact with the inner adhesive layer 7, and the innermost resin layer 82 is arranged under the adhesive contact resin layer 81, wherein the components of the adhesive contact resin layer 81 include: a mixture layer formed by 62wt% of random copolymer polypropylene with a melting point of 155°C and an MFR (230°C) of 4g / 10min, 33wt% of non-crystalline propylene elastomer and 5wt% of low-density polyethylene with a melting point of 110°C and an MFR (230°C) of 7.5g / 10min; the components of the innermost resin layer 82 include: a layer composed of random copolymer polypropylene with a melting point of 155°C and an MFR (230°C) of 15g / 10min; preferably, the thickness ratio of the adhesive contact resin layer 81 to the innermost resin layer 82 is 8:2.

[0185] Next, the performance measurement method and operation content of the outer packaging material for high-draw depth battery devices provided by the present invention will be described in detail, including the measurement of alloy composition using ICP-MS, grain size and surface orientation, tensile strength, elongation at break, 0.2% yield strength, forming depth, and aluminum foil surface wettability testing.

[0186] <Measurement method>

[0187] (1) The alloy composition was measured using ICP-MS.

[0188] Main reagents:

[0189] HNO3(high purity)

[0190] HCl(super pure)

[0191] Sample processing:

[0192] a. Weigh 0.1-0.2g of sample (accurate to 0.0001g) and add it into the solution sample cup;

[0193] b. Add 6mL of aqua regia (HCl:HNO3=3:1), shake well, fill the can and put it into the furnace cavity;

[0194] c. Microwave digestion procedure: see Table 2.

[0195] [Table 2] Microwave digestion procedure

[0196] step Temperature setting (℃) Insulation time (min) Pressure setting (atm) 1 80 2 10 2 120 2 15 3 150 2 25 4 170 2 35 5 190 30 40

[0197] Instrument parameter settings :

[0198] High frequency transmission power: 1350W, sampling extension: 7.8mm, plasma gas flow rate: 14.0L / min, auxiliary gas flow rate: 1.0L / min, nebulizer: Rabington type, nebulization temperature: 3℃, sample lifting volume: 0.4mL / min, sampling cone and intercepting cone: Ni, measurement point residence time: 0.33s, measurement point number / mass: 3, number of repetitions: 3 times.

[0199] (2) Crystal grain size and surface orientation.

[0200] The electrolytically ground material needs to be sliced ​​and then observed using EBSD: electron back diffraction.

[0201] (3) Tensile strength, elongation at break, 0.2% yield strength.

[0202] The tensile test device was used to prepare the sample with a No. 5 dumbbell-shaped punching die (SDK50294-09) and the tensile speed was 550 mm / min for measurement.

[0203] (4) Forming depth

[0204] The molding size is 80mm×70mm, the pressing pressure is 0.8MPa, the corner r=1.0mm, the convex edge r angle=1.0mm, and the convex-concave gap is 0.5mm.

[0205] [Table 3] Test solution ratio

[0206] Test solution serial number Test solution 1 Distilled water 2 Ethanol solution: distilled water = 1:9 3 Ethanol solution: distilled water = 2:8 4 Ethanol solution: distilled water = 3:7 5 Ethanol solution: distilled water = 4:6 6 Ethanol solution: distilled water = 5:5 7 Ethanol solution: distilled water = 6:4 8 Ethanol solution: distilled water = 7:3

[0207] (5) Aluminum foil surface wettability test

[0208] The National Standard of the People’s Republic of China GB / T225638.5-2016, Aluminum Foil Test Method, Part 5: Detection of Wettability is adopted.

[0209] Reagents and materials :

[0210] 1) Anhydrous ethanol (analytical grade)

[0211] 2) Distilled water

[0212] 3) Cotton wool

[0213] 4) Tweezers

[0214] 5) Test solution: Take anhydrous ethanol and distilled water and prepare the corresponding test solution according to Table 3

[0215] Test conditions

[0216] The test should be carried out at room temperature and the temperature of the aluminum foil should not be 5℃ or more higher than room temperature.

[0217] Wipe method

[0218] a. Use tweezers to pick up a cotton ball and dip it into the prepared test solution, and wipe it along the TD direction of the aluminum foil. The width of the contact surface between the cotton ball and the aluminum foil surface should not be less than 20mm, and observe the shrinkage of the test solution on the aluminum foil surface.

[0219] b. Repeated testing on the same area of ​​the aluminum foil surface is not allowed.

[0220] c. If the area wetted by the test liquid shrinks within 2 seconds, the next test liquid should be selected for retesting until the wetted area of ​​the aluminum foil surface by the test liquid does not shrink within 2 seconds, indicating that the wettability of the aluminum foil under test reaches the corresponding level of the test liquid (see Table 4).

[0221] [Table 4] Wettability grades corresponding to the test solutions

[0222] Test solution serial number Wettability Grade 1 A 2 B 3 C 4 D 5 E 6 F 7 G 8 H

[0223] (6) Aluminum foil contact angle test

[0224] The National Standard of the People's Republic of China GB / T22638.9-2008, Aluminum Foil Test Method Part 9: Determination of Hydrophilicity is adopted.

[0225] Reagents and instruments :

[0226] 1) Distilled water

[0227] 2) Contact angle meter

[0228] Determination :

[0229] a. Turn on the power of the contact angle meter and adjust the level of the contact angle meter

[0230] b. Fix the sample on the workbench

[0231] c. Add distilled water to the droplet regulator, fix the regulator on the main unit and rotate the micrometer head to make an appropriate amount of water (0.005mL-0.02mL) form a droplet on the needle, and naturally drip it onto the surface of the sample. Adjust the position of the workbench so that the droplet is in the center of the eyepiece.

[0232] d. After the water drop has been left on the sample for 60 seconds, rotate the crosshairs in the eyepiece to make a tangent line at the point where the water drop contacts the coating. The angle between the tangent line and the fixed crosshairs is the contact angle.

[0233] Several embodiments and comparative examples are listed below to further illustrate the technical features, applied technical means and expected effects of the present invention:

[0234] Example 1

[0235] The composite film was formed using the aluminum alloy foil listed in Table 5, wherein the Si content in the aluminum alloy foil was 0.04wt%, the Cu content was 0.005wt%, the Zn content was 0.008wt%, and the Ti content was 0.015wt%. The total ratio of the Cube orientation, Cu orientation, S orientation, Bs orientation, and R orientation was 72wt%, the total ratio of the Cube orientation and Cu orientation was 32%, and the Cube orientation ratio was 10%. The average crystal grain size was 9.1μm.

[0236] After annealing and degreasing, the aluminum alloy foil has a surface contact angle of 15° and a thickness of 40μm. Both sides are chemically treated in advance to form a corrosion-resistant layer.

[0237] The outer layer lamination method is as follows: the surface where the outer substrate resin layer contacts the outer layer adhesive layer is corona treated in advance. The aluminum alloy foil layer is compounded on the outer substrate resin layer by a dry compounding method. Specifically, a two-component polyurethane adhesive (polyurethane-modified polyester polyol or polyester polyol and aromatic isocyanate compound) with an NCO / OH ratio of 6.2 is coated on the corrosion-resistant layer on one side of the aluminum alloy foil to form an outer layer adhesive layer (3μm) on the aluminum alloy foil. After the outer layer adhesive layer and the outer substrate resin layer on the composite aluminum alloy foil layer, they are aged at a temperature of 80°C for 3 days to form an outer substrate resin layer (25μm) / outer layer adhesive layer (3μm) / aluminum alloy foil layer. In the following, the outer substrate resin layer / outer layer adhesive layer (3μm) / aluminum alloy foil layer is used as a composite outer substrate resin composite film.

[0238] The inner layer stacking method is as described above.

[0239] At the same time, the surface of the substrate layer was subjected to Slip coating. The Slip coating was performed by applying a 10% erucamide solution at a coating amount of 10 mg / ㎡ and then drying it.

[0240] At this time, the 0.2% yield strength was 48 MPa, the elongation in the flow direction and width direction was 25%, the elongation in the oblique direction was 36%, and the molding depth was 6.5 mm.

[0241] Example 2

[0242] The composite film was formed using the aluminum alloy foil listed in Table 5, wherein the Si content in the aluminum alloy foil was 0.016wt%, the Cu content was 0.013wt%, the Zn content was 0.004wt%, and the Ti content was 0.004wt%. The total ratio of the Cube orientation, Cu orientation, S orientation, Bs orientation, and R orientation was 77wt%, the total ratio of the Cube orientation and Cu orientation was 47%, and the Cube orientation ratio was 14%. The average crystal grain size was 6μm.

[0243] After annealing and degreasing, the aluminum alloy foil has a surface contact angle of 15° and a thickness of 40μm. Both sides are chemically treated in advance to form a corrosion-resistant layer.

[0244] The outer layer lamination method is the same as that in Example 1.

[0245] The inner layer lamination method is the same as that in Example 1.

[0246] At the same time, the surface of the substrate layer was subjected to Slip coating. The Slip coating was performed by applying a 10% erucamide solution at a coating amount of 10 mg / ㎡ and then drying it.

[0247] At this time, the 0.2% yield strength was 62 MPa, the elongation in the flow direction and width direction was 32%, the elongation in the oblique direction was 38%, and the molding depth was 8.0 mm.

[0248] [Table 5] Composition and measurement results of outer packaging materials for high-impact battery devices

[0249]

[0250] Example 3

[0251] The composite film is formed using the aluminum alloy foil recorded in Table 5. The Si content, Cu content, Zn content, and Ti content in the aluminum alloy foil are 0.03wt%, 0.007wt%, 0.006wt%, and 0.01wt%. The total ratio of Cube orientation, Cu orientation, S orientation, Bs orientation, and R orientation is 73%, the total ratio of Cube orientation and Cu orientation is 36%, and the Cube orientation ratio is 12%. The average crystal grain size is 7μm. After annealing and degreasing, the aluminum alloy foil has a surface contact angle of 15° and a thickness of 40μm. Both sides are chemically treated in advance to form a corrosion-resistant layer.

[0252] The outer layer lamination method is the same as that in Example 1.

[0253] The inner layer lamination method is the same as that in Example 1.

[0254] At the same time, the surface of the substrate layer was subjected to Slip coating. The Slip coating was performed by applying a 10% erucamide solution at a coating amount of 10 mg / ㎡ and then drying it.

[0255] At this time, the 0.2% yield strength was 50 MPa, the elongation in the flow direction and width direction was 25%, the elongation in the oblique direction was 36%, and the molding depth was 7.2 mm.

[0256] Example 4

[0257] The composite film was formed using the aluminum alloy foil described in Table 5, wherein the Si content in the aluminum alloy foil was 0.01wt%, the Cu content was 0.02wt%, the Zn content was 0.003wt%, the Ti content was 0.003wt%, and the Sb content was 0.05wt%. The total ratio of the Cube orientation, Cu orientation, S orientation, Bs orientation, and R orientation was 80%, the total ratio of the Cube orientation and Cu orientation was 48%, and the Cube orientation ratio was 20%. The average crystal grain size was 2μm.

[0258] After annealing and degreasing, the aluminum alloy foil has a surface contact angle of 15° and a thickness of 40μm. Both sides are chemically treated in advance to form a corrosion-resistant layer.

[0259] The outer layer lamination method is the same as that in Example 1.

[0260] The inner layer lamination method is the same as that in Example 1.

[0261] At the same time, the surface of the substrate layer was subjected to Slip coating. The Slip coating was performed by applying a 10% erucamide solution at a coating amount of 10 mg / ㎡ and then drying it.

[0262] At this time, the 0.2% yield strength was 64 MPa, the elongation in the flow direction and width direction was 34%, the elongation in the oblique direction was 39%, and the molding depth was 8.2 mm.

[0263] Due to the addition of Sb in the alloy composition, the crystals in the aluminum alloy foil are refined, the elongation at break is increased, and the formability of the aluminum-plastic film is improved.

[0264] Comparative Example 1

[0265] The composite film was formed using the aluminum alloy foil listed in Table 5, wherein the Si content in the aluminum alloy foil was 0.07wt%, the Cu content was 0.002wt%, the Zn content was 0.02wt%, and the Ti content was 0.03wt%. The total ratio of the Cube orientation, Cu orientation, S orientation, Bs orientation, and R orientation was 65%, the total ratio of the Cube orientation and Cu orientation was 27%, and the Cube orientation ratio was 7%. The average crystal grain size was 12μm.

[0266] After annealing and degreasing, the aluminum alloy foil has a surface contact angle of 15° and a thickness of 40μm. Both sides are chemically treated in advance to form a corrosion-resistant layer.

[0267] The outer layer lamination method is the same as that in Example 1.

[0268] The inner layer lamination method is the same as that in Example 1.

[0269] At the same time, the surface of the substrate layer was subjected to Slip coating. The Slip coating was performed by applying a 10% erucamide solution at a coating amount of 10 mg / ㎡ and then drying it.

[0270] At this time, the 0.2% yield strength was 40 MPa, the elongation in the flow direction and width direction was 18%, the elongation in the oblique direction was 30%, and the molding depth was 5.1 mm.

[0271] In this comparative example, the total of the Cube orientation, Cu orientation, S orientation, Bs orientation, and R orientation ratio is less than 70%. The total of the Cube orientation and Cu orientation ratio is less than 30%. The average particle size becomes larger, reaching 12μm. At the same time, the Si, Zn, and Ti content is too much, and the Cu content is too little, resulting in a poor sliding balance of the crystal grains when the aluminum foil is stretched, a decrease in the 0.2% yield strength, and a decrease in the elongation. After being made into an aluminum-plastic film, the formability is worse than that of the embodiment.

[0272] Comparative Example 2

[0273] The composite film was formed using the aluminum alloy foil listed in Table 5, wherein the Si content in the aluminum alloy foil was 0.07wt%, the Cu content was 0.005wt%, the Zn content was 0.008wt%, and the Ti content was 0.03wt%. The total ratio of the Cube orientation, Cu orientation, S orientation, Bs orientation, and R orientation was 65%, the total ratio of the Cube orientation and Cu orientation was 32%, and the Cube orientation ratio was 8%. The average crystal grain size was 12μm.

[0274] After annealing and degreasing, the aluminum alloy foil has a surface contact angle of 15° and a thickness of 40μm. Both sides are chemically treated in advance to form a corrosion-resistant layer.

[0275] The outer layer lamination method is the same as that in Example 1.

[0276] The inner layer lamination method is the same as that in Example 1.

[0277] At the same time, the surface of the substrate layer was subjected to Slip coating. The Slip coating was performed by applying a 10% erucamide solution at a coating amount of 10 mg / ㎡ and then drying it.

[0278] At this time, the 0.2% yield strength was 52 MPa, the elongation in the flow direction and width direction was 16%, the elongation in the oblique direction was 28%, and the molding depth was 5.5 mm.

[0279] In this comparative example, although the total ratio of Cube orientation and Cu orientation is higher than 30%, the total ratio of Cube orientation, Cu orientation, S orientation, Bs orientation and R orientation is lower than 70%. As a result, the average particle size becomes larger, reaching 12μm. At the same time, the excessive content of Si and Ti leads to the deterioration of the sliding balance of the crystal grains when the aluminum foil is stretched. Although the 0.2% yield strength can be maintained, the elongation rate becomes smaller. After being made into aluminum-plastic film, the formability becomes worse than that of the embodiment.

[0280] Comparative Example 3

[0281] The composite film was formed using the aluminum alloy foil listed in Table 5, wherein the Si content in the aluminum alloy foil was 0.04wt%, the Cu content was 0.003wt%, the Zn content was 0.015wt%, and the Ti content was 0.015wt%. The total ratio of the Cube orientation, Cu orientation, S orientation, Bs orientation, and R orientation was 71%, the total ratio of the Cube orientation and Cu orientation was 28%, and the Cube orientation ratio was 8%. The average crystal grain size was 10μm.

[0282] After annealing and degreasing, the aluminum alloy foil has a surface contact angle of 15° and a thickness of 40μm. Both sides are chemically treated in advance to form a corrosion-resistant layer.

[0283] The outer layer lamination method is the same as that in Example 1.

[0284] The inner layer lamination method is the same as that in Example 1.

[0285] At the same time, the surface of the substrate layer was subjected to Slip coating. The Slip coating was performed by applying a 10% erucamide solution at a coating amount of 10 mg / ㎡ and then drying it.

[0286] At this time, the 0.2% yield strength was 38 MPa, the elongation in the flow direction and width direction was 20%, the elongation in the oblique direction was 35%, and the molding depth was 5.6 mm.

[0287] In this comparative example, the total ratio of Cube orientation, Cu orientation, S orientation, Bs orientation, and R orientation is higher than 70%. However, the total ratio of Cube orientation and Cu orientation is less than 30%. The average particle size is 10μm. At the same time, although the content of Si and Ti is moderate, the content of Cu and Zn is too little, resulting in poor sliding balance of crystal grains when the aluminum foil is stretched, and the 0.2% yield strength decreases while the elongation increases. After being made into aluminum-plastic film, the formability is worse than that of the embodiment.

[0288] The above contents involving common knowledge are not described in detail, and those skilled in the art can understand them.

[0289] The above descriptions are only some specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention shall be included in the protection scope of the present invention. The technical scope of the present invention is not limited to the contents of the specification, but must be determined according to the scope of the claims.

Claims

1. An outer packaging material for a high-impact battery device, comprising at least an outer base resin layer, an intermediate metal layer, and an inner heat-welding resin layer; the intermediate metal layer comprises an aluminum alloy foil, and the aluminum alloy foil comprises aluminum (Al), iron (Fe), silicon (Si), copper (Cu), zinc (Zn), and titanium (Ti), wherein: In the aluminum alloy foil: 1) When observing aggregate crystals with crystal orientation anisotropy using an electron beam backscattering analysis method, in the detection of the orientation distribution on the surface of the aluminum alloy foil, relative to the total of the detected anisotropic ratio and the non-anisotropic ratio, the total ratio of the Cube orientation, Cu orientation, s orientation, Bs orientation, and R orientation is 70% to 80%, wherein the ratio of the Cube orientation is 10% to 20%, the total ratio of the Cube orientation to the Cu orientation is greater than or equal to 30%, and the total ratio of the Cube orientation to the Cu orientation is less than or equal to 48%; 2) The average grain size is less than 10.0 μm; and 3) Based on the total weight of the aluminum alloy foil, the alloy components silicon (Si) are 0.01 wt% to 0.04 wt%, copper (Cu) are 0.005 wt% to 0.02 wt%, zinc (Zn) are 0.003 wt% to 0.008 wt%, and titanium (Ti) are 0.003 wt% to 0.015 wt%.

2. An outer packaging material for a high-impact battery device as claimed in claim 1, wherein: A corrosion-resistant layer is formed at least on the inner heat-welding resin layer side of the intermediate metal layer.

3. The outer packaging material for a high-impact battery device according to claim 1, wherein: An outer adhesive layer is provided between the outer base resin layer and the intermediate metal layer.

4. The outer packaging material for a high-impact battery device according to claim 1, wherein: An inner adhesive layer is provided between the middle metal layer and the inner heat-welding resin layer.

5. The outer packaging material for a high-impact battery device according to claim 1, wherein: A non-aqueous electrical device formed of the above-mentioned outer packaging material for a battery device.

6. An outer packaging material for a high-impact battery device according to any one of claims 1 to 5, wherein: The aluminum alloy foil further contains less than 0.07 wt % of antimony (Sb).

7. The outer packaging material for a high-impact battery device according to claim 6, wherein: In the aluminum alloy foil, the direction parallel to the rolling direction is the flow direction, the direction orthogonal to the rolling direction is the width direction, and the direction forming a 45 degree or 135 degree relationship with the flow direction and the width direction is the inclined direction; when a tensile test is performed at a tensile speed of 5.0 mm / min and an initial sample length of 50 mm, the 0.2% tensile strength in the flow direction, the width direction, and the inclined direction is greater than 45 MPa, the elongation at break in the flow direction and the width direction is greater than 20%, and the elongation at break in the inclined direction is greater than 35%.

Citation Information

Patent Citations

  • Aluminum alloy sheet for battery case and battery case

    CN101851715A

  • Aluminium alloy foil and production method for aluminium alloy foil

    CN110799658A

  • Outer packaging material for high-punching-depth battery device and battery

    CN112848577A

  • Aluminum alloy soft foil for molding

    JP2018115376A

  • High-formability aluminum material

    WO2007111002A1